Promiscuous activity of ornithine decarboxylase from Enterobacter hormaechei: An alternative pathway for histamine formation in fermented sausages - Wei He; Binbin Li; Kaidi Hu; Xumei Zhong; Yulin Zhang; Jiamei Yu; Jiaxin Xie; Chengtao Li; Fengqin Li; Lanlan Wu; Shuhong Li; Jianlong Li; et al. (Food Microbiology, 2027)

Integrated soil–vegetation and stoichiometric responses reveal incomplete convergence toward a natural wetland reference after farmland-to-wetland restoration in a coastal delta wetland - Yuhan Zou; Xiaohong Guo; Junbao Yu; Xue Liu; Jifa Qin; Xuehong Wang; Wei Li; Sergio Rasmann (Ecological Engineering, 2026)

Hydrogeochemical characteristics, salinization, and irrigation suitability assessment of coastal groundwater in Hainan Island, China - Yongsheng Lin; Shengzhang Zou; Li Lu; Xianyu Wei; Lianjie Fan; Jinhui Liu (Marine Pollution Bulletin, 2026)

Spermidine and melatonin ameliorate heat stress-induced decline in sheep semen quality - Shuqi Zou; Can Wang; Bo Pan; Jianpeng Qin; Yinwei Zheng; Kunlin Du; Yaozong Wei; Ao Ning; Xiangyi Chen; Xiaoyue Xiong; Tao Sun; Xiaohui Su; et al. (Theriogenology, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Occupant-responsive scheduling in a university dormitory cyber-physical system integrating hybrid air–water PVT and an air-source heat pump - Xuhong Wang; Kun Yang; Wei Zhang; Jiahong Guo; Zhangyu Li; Ruiwen Zou; Pengxu Chen; Chenyang Zhang; Yi Zhang (Energy and Buildings, 2026)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Influences of stoss-face opening configurations on irregular wave energy partition and frequency dependence across reef structures: Laboratory investigation - Hongyi Li; Cuiping Kuang; Jilong Chen; Wei Xing; Xin Cong; Jiadong Fan; Qingping Zou (Ocean Engineering, 2026)

MOF-modified Enteromorpha prolifera biochar for efficient removal of enrofloxacin from mariculture wastewater - Wei Bao; Weijun Tian; Mengyuan Zou; Ke Yang; Bingkun Liu; Minghan Li; Bingjie Huo; Xinran Yu; Xinbo Wang (Journal of Water Process Engineering, 2026)

Local oxophilicity Sm incorporation drives structural alteration of Cu2O/Cu catalyst in CO2 electroreduction - Zihao Wei; Yulin Qin; Mengbo Zou; Lin Jia; Haorun Li; Yuekun Zhang; Jinyu Wang; Zeyu Guo; Hao Wu; Zeyu Zhang; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2026)

ADAPT-Tracker: Adaptive dynamic perception and trajectory-consistent network for aerial multi-object tracking - Jian Zou; Ke Liu; Wei Zhang; Qiang Li; Qi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Role of 2-phenylethanol in regulating population density and biocontrol efficacy of Scheffersomyces spartinae W9 via quorum sensing - Siyi Wu; Xiurong Zou; Yingying Wei; Jiamei Li; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (International Journal of Food Microbiology, 2026)

Bicarbonate-enabled high-valent cobalt-oxo and singlet oxygen generation for pathway switching from radical to non-radical oxidation in Co(II)/calcium sulfite system - Junren Zhu; Juanjuan Zou; Ting Peng; Xinyi Li; Chaohan Jiang; Shiyang Bai; Wei Ding; Zhenzhen Jiang (Chemical Engineering Journal, 2026)

Oxidative ligand dissociative synthesis of highly active anti-tumor Cu2O nanoparticles from the stryker's reagent - Mengqi Li; Xiaolin Jiang; Jin Zhang; Hui Wang; Dongming Yu; Yong Li; Wei Xie; Yaru Zou; Shuming Guo; Wenyi Yang; Shizhen Zhao (Chemical Engineering Journal, 2026)

Flood regime and dam operation jointly determine cyanobacterial dynamics in deep oligotrophic-mesotrophic reservoirs - Yu Qiu; Hai Xu; Wei Zou; Guangwei Zhu; Huiyun Li; Hans W. Paerl; Zhixu Wu; Kun Shi; Mengyuan Zhu; Boqiang Qin; Yunlin Zhang; Mingliang Liu (Water Research, 2026)

River patterns reveal landscape evolution at convergent margins, Longmen Shan, eastern Tibet - Shao Liu; Wei Li; Junjie Zou; Dawei Jiang; Hao Zhang (Geomorphology, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

Rare earth element partitioning in Hadean zircons establishes granitic magma source - Xinyu Zou; Yong Zhao; Xiaocai Shan; Jilian Jiang; Ross N. Mitchell; Yi Zou; Hao Wang; Wei Yang; Zhuosen Yao; Kezhang Qin; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

A statically and dynamically stable anode interface for high-temperature lithium metal batteries - Geng Chen; Xiang Feng; Guocheng Li; Zhe Tan; Jinmin Wang; Zhiyan Wang; Guodong Zou; Qianfan Zhang; Qiuming Peng; Yuanjian Li; Wei Xiao (Chemical Engineering Journal, 2026)

Engineering the d-band center of CoSex via W-doping for efficient heterogeneous electro-Fenton process - Xinyang Sun; Fan Yang; Chunhui Yu; Kuobo Wang; Junpu An; Kexin Wei; Jiabao Guo; Binling Zou; Yongfeng Li (Chemical Engineering Journal, 2026)

Antibiotics elimination by coupling ROS-mediated bond cleavage with metabolic trade-offs in electron-driven groundwater remediation - Shuhan Xing; Fanghui Chen; Jiajun Lu; Xiaolin Zhang; Xiaodong Zhao; Jing He; Wei Zou; Xiaojing Li (Bioresource Technology, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Elastic preloading-enhanced parallel-column brace for vibration suppression of deep-sea mining towers - Shubin Ji; Li Zou; Qianxi Zhang; Cong Wang; Yingjie Wei; Zongbing Yu (Ocean Engineering, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Mining rare earth elements with ammonium sulfate as a leaching agent provokes a significant perturbation in soil microbial function - Yong-He Han; Ming-Zhu Zou; Xue-Mei Wei; Xian Chen; Li-Chao Tong; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2026)

Valorization of desulfurization sulfur paste for enhanced mixotrophic denitrification in a stratified fluidized-bed bioreactor - Wei-Zhe Chen; Tian-Hu Chen; Ya-Qian Li; Xue-Hua Zou; Hai-Bo Liu; Yue-Fei Zhou (Journal of Environmental Chemical Engineering, 2026)

Hydrological regime modulates nitrogen retention-removal shifts in a glacier-oasis alpine river by restructuring multi-trophic interactions and microbial assembly - Yifei Fan; Qiqi Wei; Pan Zhang; Li Zou; Ayixie Aisikaier; Xiaoyun Ma; Zetao Dai; Yunfeng Tian; Yujie Li; Feifei Wang; Shengchang Yang; Wenzhi Cao (Journal of Environmental Management, 2026)

Petrology and geochemistry of monzogranite and porphyritic granite in Laowan ore field of Qinling orogenic belt, China: Implications for gold and molybdenum mineralization - Ying-nan Chen; Cheng Xu; Wen-lei Song; Wei Fu; Ze-bang Yi; Zhi-xuan Han; Chengyu Zou; Jian-li Chen (Journal of Asian Earth Sciences, 2026)

Catalytic tar cracking over calcium oxide-based bifunctional materials during biomass chemical looping gasification: Experimental and DFT approaches - Li Zou; Li Ma; Gaoming Wei; Shifeng Deng; Qinxin Zhao (Fuel, 2026)

A novel Camellia oil microemulsion significantly enhances the bioaccessibility and antioxidant activity of curcumin: a comparative study with macroemulsion - Jingyi Chen; Jiayi Zou; Yuting Yang; Wei Li; Qihui Shui; Man Tian; Yu Zhou; Xingfa Han; Tao Chen; Lijun Zhou (Food Chemistry, 2026)

Molten salts as ionic reaction fields for two-dimensional catalysts: From precursor transformation to catalytically relevant interfaces - Wei Xia; Lei Yang; Qianqian Zou; Jingjing Li; Min Wei; Gan Meng; Tengfei Xiang; Chunchen Yuan; Lijun Zhang; Hong Hu; Xiangyu Liu; Xiaoyong Zhang; et al. (Chemical Engineering Journal, 2026)

Multiscale structure and wettability changes of different rank coals under short-term supercritical CO2 treatment: Implications for CBM enhanced recovery and carbon sequestration - He Li; Jieyan Cao; Jiexin Lu; Quanle Zou; Shiliang Shi; Wei Yang; Xianzhong Li; Zheng Wang (Chemical Engineering Journal, 2026)

Cellulose/polyester-blended microplastics amplify plastisphere pathogen and antibiotic resistome risks - Keyang Jiang; Xinru Pan; Sijia Zhu; Zewen Dang; Zhenzhen Yang; Liangyu Huang; Xiaochen Pan; Xuelian Zou; Jian Zhang; Yanzhu Guo; Wei Zhang; Zhi Li; et al. (Bioresource Technology, 2026)

Targeting eHsp90α/GRP78 signaling-mediated endothelial barrier dysfunction in diabetic atherosclerosis: evidence from clinical and experimental studies - Yan Qiu; Hejia Zhao; Xinyi Ding; Guozhen Wu; Mengyi Cai; Shuxian Li; Jingjing Liang; Liwen Chen; Xianbo Wu; Wei Li; Peng Zhu; Fei Zou; et al. (Molecular and Cellular Biochemistry, 2026)

Liposome-iRGD loaded with astragaloside IV alleviates the functional damage of endothelial progenitor cells via the Hippo-YAP/TAZ signaling pathway - Churuo Zeng; Qinxia Li; Dongwei Guo; Wu Xiong; Xiaoling Zou; Wei Li; Jie Bin; Xiuping Wang; Zihao Zhang; Bingqian Xue; Ruowei Hu; Xi Zhang (In Vitro Cellular & Developmental Biology - Animal, 2026)

Sulfadiazine degrading bacteria Vibrio alginolyticus isolated from mariculture wastewater: Performance, degradation pathways, and mechanisms based on transcriptomic analysis - Xinran Yu; Minghan Li; Weijun Tian; Mengyuan Zou; Bingkun Liu; Bingjie Huo; Xinbo Wang; Wei Bao; Ke Yang (Marine Pollution Bulletin, 2026)

Statistical analysis of freak waves characteristics under tropical cyclone influence in open ocean conditions - He Bian; Xinran Ji; Zhiwen Cai; Zhong Peng; Li Zou; Qiaofeng Ma; Wei Jia (Ocean Engineering, 2026)

Organic fertilizer substitution combined with Bacillus velezensis SQR9 inoculation reduces carbon footprint and enhances net eco-economic benefits in tropical vegetable fields - Wei Tian; Huacheng Yin; Ziheng Zou; Rong Li; Yawen Huang; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Journal of Environmental Management, 2026)

Spatiotemporal changes of salt crusts in the Ebinur Lake Basin (2005–2025) using a non-linear spectral unmixing model - Chen-Wei Wang; Xiao-Xiao Zhang; Xiao-Ming Cao; Yi-Ming Feng; Jia-Qiang Lei; Sheng-Yu Li; Jia-Xiu Zou; Jie Zhou; Lian-You Liu; Zi-Fa Wang; Xiao Tang (Journal of Arid Environments, 2026)

Mg anode-assisted photocatalytic fuel cell system for antibiotic/ nitrogen/ phosphorus removal and simultaneous electricity generation in seawater - Bingjie Huo; Weijun Tian; Bingkun Liu; Mengyuan Zou; Minghan Li; Xinran Yu; Xinbo Wang; Wei Bao; Ke Yang (Desalination, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Metabolites from Trichoderma amazonicum AF2115A by monoculture and coculture with Fusarium oxysporum A11F(B) - Wei-Cheng Xu; Yin-Ping Song; Ji-Xue Zou; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2026)

Analysis of vibro-acoustic scattering problems using enriched overlapping finite elements - Qiang Gui; Zhilong Jiang; Zhihong Zou; XiangYu You; Kai H. Luo; Yingbin Chai; Wei Li (Ocean Engineering, 2026)

Experimental study on wave attenuation performance and motion responses of a water ballast type floating breakwater - Xinran Ji; Xudong Gao; Wei Jia; Aoming Tang; Li Zou (Ocean Engineering, 2026)

Deep removal of iron from quartz via SDS-enhanced HCl leaching: Wetting and penetration mechanism - Long Ren; Kuixian Wei; Shicong Yang; Wenhui Ma; Junjie Zhao; Guangying Zhang; Ruizhe Wang; Yangwei Zou; Baitong Li (Minerals Engineering, 2026)

Influence of light irradiance on the toxicity of graphitic carbon nitride to algae: Intensified nano-bio interactions driven by particle reassembly - Yuhan Huo; Xingli Zhang; Xiaokang Li; Guoqing Zhang; Caixia Jin; Wei Zou (Journal of Environmental Sciences, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Dual-network synergistic lignin-based polyurethane elastomers with high strength, toughness, and broad-temperature-range damping - Debiao Fu; Xing Su; Shenglin Wei; Jialu Shang; Xiaodong Li; Jin Xu; Tianhao Wu; Wei Zhang; Hao Jiang; Dichang Xue; Lu Jin; Kai Liu; et al. (Chemical Engineering Journal, 2026)

Design principles of non-copper catalysts for electrochemical CO2-to-C2+ conversion: Molecular sites, interfaces, and mechanisms - Wei Xia; Yangchen Hu; Xiaosheng Hu; Jingjing Li; Lei Yang; Qianqian Zou; Lili Ding; Linhuan Wei; Lijun Zhang; Chunchen Yuan; Xiangyu Liu; Fan Huang; et al. (Chemical Engineering Journal, 2026)

Potential Impact of Macromolecular Structure and Nanoscale Pore on Coal Matrix Subjected to Microwave–LN2 Freeze–Thaw Cycles - Xi Wu; He Li; Huihui Liu; Quanle Zou; Jiexin Lu; Junhui Mou; Baiquan Lin; Wei Yang; Jieyan Cao (Natural Resources Research, 2026)

Integrated Transcriptomic and Proteomic Analyses Reveal Stage-Dependent Gill Remodeling Under Chronic Salinity Stress in Grass Carp (Ctenopharyngodon idella) - Jinglin Zhu; Wei Xiao; Dayu Li; Jie Yu; Binglin Chen; Hong Yang; Zhiying Zou (Marine Biotechnology, 2026)

An optimization study of bit stick-out in a deepwater conductor jetting project based on a pipe-string model - Lei Li; Yi Wu; Tiancong Cui; Xin Zou; Shiming Wei; Chiheng Zhu; Jiatong Jiang (Ocean Engineering, 2026)

Ensemble LSTM models for short-term early warning of nitrous oxide emissions: A case study of a full-scale wastewater treatment plant in Copenhagen - Yangyang Guo; Anlei Wei; Hanxiao Shi; Zixuan Wang; Shengbo Yue; Xiaofan Chang; Kangrong Tang; Jirui Zou; Nan Li (Journal of Water Process Engineering, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Eco-friendly plant-enzyme-induced mineralization coatings for corrosion protection of low-carbon steel - Xuanhua Feng; Jiayi Li; Yuxuan Zou; Yiran Gao; Jie Wei; Cheng Wang; Ruixing Wang (Journal of Cleaner Production, 2026)

Tobacco-rice rotation drives soil microbial communities to establish a “nicotine-molybdenum (Mo)-nitrogen” coupling metabolic network - Xuan Li; Fan Zhuang; Shaolong Wu; Xiaohui Huang; Yansong Xiao; Xiangping Zhou; Kai Teng; Yiqiang Chen; Wei He; Zhengyu Deng; Qi Huang; Can Wang; et al. (Journal of Environmental Management, 2026)

Doping Ru on Ni2P with phosphorus vacancies for overall seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Taotao Ai; Xiangyu Zou; Wenhu Li; Sumin Wang; Weiwei Bao; Jie Han (Fuel, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Optimal dietary pyridoxine requirement of oriental river prawn (Macrobrachium nipponense): Insights from growth, feed utilization, and protein metabolism - Yan-Zou Dong; Lu-Yao Wei; Wen-Bin Liu; Bo Liu; Cun-Xin Sun; Xiang-Fei Li (Animal Feed Science and Technology, 2026)

Genome-wide association study identifies candidate genes and functional pathways associated with salinity tolerance in grass carp (Ctenopharyngodon idella) - Xinbin Hou; Binglin Chen; Zhiying Zou; Jinglin Zhu; Dayu Li; Jie Yu; Hong Yang; Wei Xiao (Conservation Genetics Resources, 2026)

Phase separation of the redox sensor RCD1 mediates differential ROS signals to regulate plant growth and stress responses - Jingjing Xing; Kaiwen Li; Wenwen Duan; Zhikun Duan; Yu Zhang; Aiyu Guo; Suting Wang; Ning Ding; Yaling Zou; Xiaobin Wei; Xiaoliang Zhao; Junli Zhang; et al. (Molecular Plant, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Fe@Fe2O3 pretreatment enhanced production of short-chain fatty acids from anaerobic sludge fermentation: Elucidating hydrolysis-acidification performance and mechanisms - Jinbao Xu; Jipeng Zou; Xiaowei Zhang; Sifeng Jian; Liang Zuo; Peiyao Song; Linqing Qiu; Wei Li; Yongkang Dai; Yongsheng Chen; Lei Miao; Gang Guo; et al. (Journal of Environmental Chemical Engineering, 2026)

Tripolyphosphate-enhanced Fe-C promotes O2 activation for bisphenol A removal: Roles of tripolyphosphate and dominant reactive oxygen species - Xiang Li; Mengke Zhang; Huajing Song; Qingge Cui; Yuwei Pan; Zhenglong Li; Wei Zou (Journal of Environmental Chemical Engineering, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Insights into the copigmentation effect and mechanism of five carbohydrates on thermal and color stability of mulberry anthocyanins - Qian Li; Xuanran Lin; Zhengguang Wang; Dongxu Xing; Fan Liu; Qingyi Wei; Yuxiao Zou (Food Chemistry, 2026)

Construction of novel porous starch microparticles loaded with curcumin oleogel: Improving colon-targeted delivery potential of curcumin - Li Ma; Dian Liu; Yujia Xu; Qun Liu; Jing Zhou; Chuchu Zhang; Erihemu; Xiaojiang Wu; Liqiang Zou; Wei Liu (Food Chemistry, 2026)

Rapid urine protein detection for CKD diagnostics using a high-sensitivity PDA-coated infrared fiber sensor - Shun Li; Ting Fang; Yongkun Zhao; Yinsheng Xu; Yami Ling; Ming Wang; Xiangpan Li; Jiang Zou; Wei Xiao; Guangchao Zang; Xianghua Zhang (Chemical Engineering Journal, 2026)

Fabricating nano- and micro- pesticide delivery systems using environmentally friendly humic acid - Kun Zhuang; Yue Xu; Zijun Wang; Xin Liu; Yunyu Tang; Xiangyang Li; Guang Wei; Hongyu Cao; Tingting Zhai; Feng Liu; Nan Zou; Peng Zhang; et al. (Chemical Engineering Journal, 2026)

Crop rotation benefits for nitrogen-oxide mitigation and soil health in tropical vegetable fields - Wei Tian; Feilong Liang; Rong Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Agriculture, Ecosystems & Environment, 2026)

Dietary transitions and manure recycling could halve nitrogen pollution from grain crops in China - Yanliang Li; Huihang Sun; Yuelei Li; Weijia Li; Zhilei Xie; Yanan Zou; Xiang Li; Wei Zuo; Yu Tian; Lipin Li (Agricultural Systems, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Enhanced removal of submicron gas–liquid inclusions from vein quartz via microwave-assisted roasting - Yangwei Zou; Junjie Zhao; Guangying Zhang; Baitong Li; Long Ren; Shicong Yang; Kuixian Wei; Wenhui Ma (Minerals Engineering, 2026)

Multimodal machine learning for Cr(Ⅵ) removal and floc settling using image-based floc features and operating parameters - Yaqi Zhu; Anlei Wei; Jirui Zou; Hanxiao Shi; Hao Hu; Zixuan Wang; Kangrong Tang; Nan Li (Journal of Environmental Management, 2026)

Lacto-N-triose II alleviates metabolic dysfunction-associated Steatotic liver disease via microbiota-dependent citrulline biosynthesis - Kaiwei Chen; Huiqing Yu; Bei Liu; Zizhen Yang; Wei Zhang; Yu Tian; Zhinan Wu; Haoyu Wang; Liang Xiao; Yiyi Zhong; Haifeng Zhang; Xu Fang; et al. (Food Research International, 2026)

Bio-organic fertilization promotes soil nutrient cycling and reduces CO2 emissions via regulating bacterial communities in vegetable production system - Lijun Ren; Lili Dong; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (European Journal of Soil Biology, 2026)

Remediation of mine farmland soil using hydrothermal carbonization aqueous phase from Baijiu distillers' grains: integrated benefits of metal detoxification and fertility enhancement - Piao Yang; Tao Liu; Changlan Hou; Liming Liu; Jie Hu; Cheng Huang; Wei Zou; Caixia Li; Yugui Chen; Hongmei Luo; Yunbo Zhai; Linglin Xie (Environmental Research, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

LLZTO ceramic particles regulate in situ polymerization of hybrid electrolytes and enable stable cycling of Li metal batteries - Peize Li; Qiyao Zou; Hanwei Liu; Wei Zhou; Chao Wang; Yuying Zhang; Liting Deng; Chi-Ying Vanessa Li; Chunzhen Yang (Chemical Engineering Journal, 2026)

An integrated ultrasonic and cellulase pretreatment strategy: simultaneously enhancing medium-chain fatty acid production and reducing antibiotic resistance genes in anaerobic digestion of animal manure - Bingni Wei; Li Zhang; Haoxiang Zhang; Bojun Gui; Qiuqing Deng; Xuan Chang; Peng Yu; Xianwen Dong; Bing Zou; Xiaoli Zhang; Yongju Zhao; Zhongquan Zhao; et al. (Bioresource Technology, 2026)

Integrating fish mint (Houttuynia cordata Thunb.) floating beds and feed additives to improve health and disease resistance in Nile tilapia - Menglin Yu; Binglin Chen; Zhiying Zou; Jinglin Zhu; Dayu Li; Jie Yu; Hong Yang; Wei Xiao (Animal Feed Science and Technology, 2026)

Comparative analysis of disease resistance and immune responses in four intraspecific hybrids of Nile tilapia challenged with Streptococcus agalactiae - Yuchen Wang; Zhiying Zou; Jinglin Zhu; Wei Xiao; Dayu Li; Jie Yu; Binglin Chen; Hong Yang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Experimental study on wave breaking characteristics over three-dimensional reef island topography - Wei Jia; Yu Xiao; Xinran Ji; Li Zou; Shuxue Liu (Ocean Engineering, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Spatial disparities and policy implications of urban-ecosystem coupling: A case study from the southern China - Wei Zou; Baojing Wei; Xijun Hu; Cunyou Chen; Qizhen Li; Jia Tang; Shiyi Cao (Journal of Cleaner Production, 2026)

Integrated multistage process optimization and photovoltaic electro-fenton synergy for enhanced efficiency and energy savings in wastewater treatment - Xiding Zeng; Wei Zhang; Ruiwen Zou; Jiahong Guo; Kun Yang; Zhangyu Li (Journal of Environmental Management, 2026)

Tailoring pore architecture and functionality in COF-based mixed-matrix membranes for high-efficiency CO₂ capture - Linsheng Wei; Junda Dong; Yanshu Lu; Wenlin Zhou; Xing Chen; Wenfeng Tu; Jincheng Li; Binchun Zou; Guoji Huang (Journal of Environmental Chemical Engineering, 2026)

DVGBench: Implicit-to-explicit visual grounding benchmark in UAV imagery with large vision–language models - Yue Zhou; Jue Chen; Zilun Zhang; Penghui Huang; Ran Ding; Zhentao Zou; PengFei Gao; Yuchen Wei; Ke Li; Xue Yang; Xue Jiang; Hongxin Yang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Late-Quaternary activity of parallel normal faults along the southern margin of the Yuguang Basin in the Shanxi Rift, China and its seismogeological implications - Junjie Zou; Feng Shi; Honglin He; Zhigang Shao; Wenqiao Li; Yoshiki Shirahama; Zhanyu Wei; Jianhua Huang (Geomorphology, 2026)

Upwelling enhances cycling and emissions of very short-lived halocarbons: Biogeochemical mechanisms and climate feedbacks - Ya-Wen Zou; Qin-Sheng Wei; Cheng-Xuan Li; Xing Zhai; Ming Xin; Xiao-Meng Duan; Hui Ding; Baodong Wang (Global and Planetary Change, 2026)

Numerical investigation on combustion behavior of an X-type rotary engine: Impact of hydrogen enrichment and engine speed - Run Zou; Lei Zhang; Ting Hou; Yanhong Zhou; Wei Yang; Lijun Lei; Feng Li (Fuel, 2026)

Research review of underground coal gasification: principles, challenges and prospects - Daxing Wang; Jijun Tian; Shuguang Yang; Jiaqun Zou; Bo Wei; Xin Li; Hanyu Tong; Yufei Zhang; Chengjie Xu (Fuel, 2026)

Activating water via precisely patterned wettability domains for low-enthalpy evaporation with a lotus-seed-pod inspired hydrogel - Qian Chen; Xiaoke Li; Size Zheng; Lie Zou; Wei Xie; Xinrong Huang; Hongbing Wang; Mingming Zheng; Yingtang Zhou (Chemical Engineering Journal, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

Molecular mechanisms of cold stress-induced energy stress, cholesterol metabolic disorders, and apoptosis in Pangasianodon hypophthalmus - Dongjie Wang; Min Li; Min Liao; Yao Tian; Qing Wu; Shaolin Xie; Wei Luo; Jixing Zou; Jun Shi; Zongjun Du (Aquaculture, 2026)

Are iron and manganese key factors in nitrate attenuation within the shallow groundwater of the nitrogen attenuation zone? - Qiwen Xia; Jiangtao He; Baonan He; Binghua Li; Cong Yan; Wei Li; Hua Zou; Chenchen Tao; Zhen Chen; Shuo Ma (Water Research, 2026)

FTH1-mediated iron dysregulation and ferroptosis in manganese-induced neurotoxicity - Xiaoli Ma; Shengtao Wei; Fangfei Li; Guiqiang Liang; Jian Wang; Yunfeng Zou (NeuroToxicology, 2026)

A double-package delivery system based on κ-carrageenan hydrogels and vitamin E/highly branched cyclic dextrin composites: Structural characteristics and release behavior - Wentao Ma; Wei Liu; Chao Yuan; Bo Cui; Yaqi Liu; Li Guo; Bin Yu; Meng Zhao; Feixue Zou (Food Chemistry, 2026)

Numerical simulation of rock creep and failure using a Norton-Bailey-based four-dimensional lattice spring model - Xin-Dong Wei; Muhammad Shoaib; Tao Zhou; Yuhang Wu; Zhe Li; Yang Zou; Gao-Feng Zhao (Computers and Geotechnics, 2026)

Ru-based catalyst with controlled loading on CeMOF nanoislands for reductive amination of furfural to furfurylamine - Yan Pan; Siyi Pu; Ying Wang; Wei Yan; Yang Li; Haoran Ming; Chungang Min; Xiaoqin Zou; Changfu Zhuang (Chemical Engineering Journal, 2026)

Targeted and stimuli-responsive gene/drug synergistic therapeutic system based on pcDNA3.1-Mmp13 and hydroxychloroquine for the effective treatment of liver fibrosis in mice - Li-Shuang Hou; Jin-Yi Zhao; Yan-Qi Zou; Yao-Wen Zhang; Jie-Hua Xing; Wei He; Si-Yuan Zhou; Bang-Le Zhang (Chemical Engineering Journal, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Prioritizing alternative halogenated flame retardants in mangrove spiders: high maternal transfer toxicity outweighs low environmental burden - Qiang Xie; Lvyan Tan; Congmo Jin; Wei Wei; Fenglong Jia; Yuping Wu; Haoyu Jiang; Shichun Zou; Baowei Chen; Tiangang Luan; Lihua Yang; Li Lin (Archives of Toxicology, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Contact-induced high energy-dissipation array column for vibration suppression of deep sea mining tower - Shubin ji; Li Zou; Zhe Sun; Xueyu Wang; Maoyue Lin; Cong Wang; Yingjie Wei (Ocean Engineering, 2025)

Temporal and spatial variations of redox conditions in the middle Triassic Chang 7 member of the Yanchang formation, Ordos Basin, North China - Hanlin Liu; Yuangeng Huang; Xiangdong Zhao; Wei Wang; Xincheng Qiu; Zhen Qiu; Juan Han; Zhen Shen; Yujie Li; Ganlin Hua; Zhong-Qiang Chen; Caineng Zou (Marine and Petroleum Geology, 2025)

Ecological drivers and functional roles of phage communities in the Yangtze River’s freshwater ecosystems - Liang Peng; Fengxia Yang; Jing Zhang; Jiayu Shang; Wei Xu; Shoushan Sheng; Qinfen Li; Yukun Zou; Zhengfu Yue (Journal of Hazardous Materials, 2025)

Natural Fe-bearing clay mineral enhanced Fe reduction, pollution attenuation and biotic-abiotic linkage in sediments - Hong Qin; Ying Zeng; Piao Xu; Zhen Wei; Fuqi Wu; Ziwei Wang; Han Wang; Jing Gao; Jiaqi Li; Zhibang Zou (Journal of Hazardous Materials, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Transcription factor SmMYC2 regulates secondary cell wall thickening to enhance drought resilience in eggplant - Sirui Li; Zhi Qiao; Xinxin Zhang; Min Zou; Yao Hu; Dayong Wei; Qinglin Tang; Yang Yang; Zhimin Wang (Plant Cell Reports, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Genome-wide identification and expression analysis of PP2C gene families in two Chimonanthus species - Xin-Chen He; Jie-Xin Shao; Wei Zou; Shu-Xiao Zhang; Li Zhu; Meng-Cheng Ji; Cui-Hua Gu; Li-Yuan Yang (Genetica, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Hot moment emissions of N2O suppressed by higher native soil organic matter - Zhichao Zou; Yue Li; Huanhuan Wei; Zhangliu Du; Xiaotang Ju; Di Wu (Soil Ecology Letters, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

The role of mineral mediation in organic carbon preservation and phosphorus removal in saline lake sediments of the Tibetan Plateau - Dongli Li; Haicheng Wei; Yafei Zou; Xu Wang; Qian Bao; Ronglei Duan; Xiaoyu Gong; Jingfu Wang; Haiquan Yang; Min Zhao; Songtao Li; Haibo He (Journal of Hydrology, 2025)

Phase transformation and removal mechanism of iron impurities in vein quartz during ammonium sulfate roasting - Baitong Li; Guangying Zhang; Junjie Zhao; Yangwei Zou; Long Reng; Shicong Yang; Kuixian Wei; Wenhui Ma (Journal of Cleaner Production, 2025)

MOSAIC-Tracker: Mutual-enhanced Occlusion-aware Spatiotemporal Adaptive Identity Consistency network for aerial multi-object tracking - Jian Zou; Wei Zhang; Qiang Li; Qi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Lactobacillus plantarum P9 encapsulated in gelatin/gellan gum microcapsules with lipid filling and Ca2+ crosslinking: Enhancing digestive vitality and storage stability - Youfa Xie; Kui Zhang; Xiaojuan Ma; Yang Zhang; Xiuying Wu; Li Ma; Liqiang Zou; Wei Liu (Food Bioscience, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Modulating the redox states in a 3D conductive MOF for sweat ascorbic acid monitoring - Wei-Qi Wang; Han Xie; Feng Cheng; Ting Zou; Ke-Qiang Xu; Amare Aregahegn Dubale; Wen-Hui Zhang; Ning Xu; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

NIR fluorescent substrate-driven discovery of prolyl endopeptidase natural inhibitors and its inhibition of alpha-synuclein aggregation and promotion of autophagy - Jing Zhang; Kun-Jie Bian; Yi-Jing Wang; Xing-Kai Qian; Jin Geng; Hai-Dong Guo; Li-Wei Zou (Chemico-Biological Interactions, 2025)

Unequal opportunities and green transition: A study on the mechanism of green total factor productivity differences in China’s regional marine economy - Caizhi Sun; Xinyi Li; Wei Zou; Yudi Yang (Regional Studies in Marine Science, 2025)

Straw humification coefficient and its relation to soil carbon and nitrogen status - Yue Sun; Huiying Wang; Wei Jia; Keyu Ren; Bingjie Li; Hongqin Zou; Yinghua Duan; Minggang Xu (Journal of Environmental Management, 2025)

Multi-temporal feature reconstruction of N2O time series for machine learning prediction in wastewater treatment plants: Enhanced predictability and physically-informed interpretability - Zixuan Wang; Anlei Wei; Kangrong Tang; Jirui Zou; Hanxiao Shi; Yaqi Zhu; Hao Hu; Nan Li (Journal of Environmental Chemical Engineering, 2025)

Lipidomics revealed the geographical origin and breed variability of sheep milk - Hai-Long Wang; Xiaoyin Chen; Xiaoyu Peng; Yu Gao; Jiaqi Wang; Wei Li; Chinping Tan; Yuan fa Liu; Wenjun Zou; Yong-Jiang Xu (Food Bioscience, 2025)

ClavF derived from Clavanins as a promising candidate for fighting infections from multiple-drug resistance Aeromonas hydrophila - Zhihao Peng; Chao Wei; Bin Li; Minzhi Chen; Hongquan Wang; Zhaoxia Zou; Jinjun Chen (Fish & Shellfish Immunology, 2025)

Energy efficiency analysis and life cycle assessment of a biosafety level 4 laboratory - Ruiwen Zou; Wei Zhang; Jiahong Guo; Xiding Zeng; Kun Yang; Zhangyu Li; Xuhong Wang (Energy and Buildings, 2025)

Self-activated antibacterial mask through respiratory induced deformation and temperature variation - Liqi Wei; Li Liu; Qin Zhang; Wenye Xie; Zhiqi Yang; Xin Liu; Yunan Yang; Yining Chen; Yiping Ren; Tianshu Zou; Biao Zhang; Hongxia Ma; et al. (Chemical Engineering Journal, 2025)

Orally administered milk-derived extracellular vesicles alleviate hepatic metabolic dysfunction by targeting hepatocytes and modulating ER stress - Rui Zhang; Haoran Wang; Guoyue Wei; Xipeng Sun; Yifan Zou; Chaoting Wen; Tao Li; Huaxi Yi; Lingjun Tong (Chemical Engineering Journal, 2025)

Mechanically responsive self-reinforced polyurethane elastomers with cyclodextrin metal-organic framework structure for high impact resistance - Jing Lv; Xiaodong Li; Ni Zhai; Tianhao Wu; Chengwang Shi; Hong Yu; Wei Zhang; Tenglong Ma; Hao Jiang; Meishuai Zou (Chemical Engineering Journal, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Assessment of the efficacy of Corbicula fluminea in controlling Ichthyophthirius multifiliis infections - Tian Qin; Yang-Yang Pan; Ke Huang; Wei-Shan Zhao; Ying-Zi Pan; Hong Zou; Wen-Xiang Li; Shan-Gong Wu; Gui-Tang Wang; Ming Li (Aquaculture, 2025)

Moderate ozone application preserves postharvest quality of ‘manaohong’ cherries by enhancing antioxidant defense and membrane stability - Wei Zou; Ning Ji; Yuxin Li; Huali Nie; Qi Gao; Rui Wang; Cunkun Chen; Bangdi Liu (Journal of Stored Products Research, 2025)

Synergistic effect on sludge disintegration and antibiotic resistance genes removal during sludge treatment by combined plasma-calcium peroxide - Tengfei Li; Shuang Li; Jingqi Xu; He Guo; Zhiyin Ren; Wei Zou; Tiecheng Wang (Journal of Hazardous Materials, 2025)

Characterizing the interaction of N2O and CO with and without hydrogen addition using outwardly propagating spherical flames - Jiabiao Zou; Jianguo Zhang; Wei Li; Yuyang Li; Aamir Farooq (Fuel, 2025)

Improving mineral bioaccessibility and balancing physical stability in soymilk through bioprocessing - Wei Chen; Fengru Zhang; Jia Hao; Xiaoyu Li; Wenwen Lv; Kaiyi Zou; Hua Wu; Junsong Xiao; Yanbo Wang; Duoxia Xu (Food Chemistry, 2025)

Monitoring probiotic viability in vivo using DNA nanodevice-decorated bacteria - Siqi Zou; Li Yang; Ruoting Tang; Wumiti Aihemaiti; Ziang Cheng; Jiaxiong Li; Wei Tao; Yue Huang; Jiehua Ma; Chao Li (Chemical Engineering Journal, 2025)

Scalable synthesis of anatase TiO2 nano-in-micro spheres for hybrid sodium-ion capacitors - Zerui Yan; Sicheng Fan; Xia Zou; Qinyao Jiang; Dafu Tang; Kun Lan; Jiaxin Li; Yingbin Lin; Zhigao Huang; Dong-liang Peng; Qiulong Wei (Chemical Engineering Journal, 2025)

Corrigendum to “Zinc isotopic composition of oceanic crust: Insights from oceanic gabbro cumulates and MORBs” [Chemical Geology 670 (2024) 122443 1–13] - Xia Wang; Zaicong Wang; Jakub Ciazela; Zongqi Zou; Wei Li; Yuanyang Yu; Ming Li; Yongsheng Liu (Chemical Geology, 2025)

KIAA1522 isoform switching regulates LTR-RTs activity in distinct pluripotency states of hESCs - Ning Yang; Wen Sun; Shiwei Cao; Chen Zhao; Nannan Wang; Pengcheng Li; Yu Zou; Siqi Wang; Tongtong Cui; Shuyu Guo; Wei Li; Haoyi Wang; et al. (Science China Life Sciences, 2025)

Enhanced ELISA detection by target protein enrichment with MIP: A new strategy for ultra-sensitive protein detection - Yafei Wang; Haitao Wang; Yan Zhang; Wei Li; Sijia Gao; Jiyan Qiao; Lei Zou; Zhuo Zhao; Ying Guan; Yongjun Zhang (Analytica Chimica Acta, 2025)

Accelerated photo-Fenton degradation of ciprofloxacin on CoSx@TiO2 amorphous-crystalline interface with S-O bond bridging - Yani Zhu; Jinyang Li; Yuhang Lai; Yisheng Cao; Jiayi Li; Zhihui Wei; Lixia Yang; Zhenglin Chen; Jianping Zou (Environmental Research, 2025)

Recent progress of proline endopeptidase ligands and their effects on protein-protein interactions - Kun-Jie Bian; Xiaoze Bao; Xiao-Dong Li; Damien Bonne; Li-Wei Zou (Chemico-Biological Interactions, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Chlorination treatment actuated structural reconstitution and aggravated toxicity of molybdenum disulfide nanosheets to freshwater algae - Qian Wang; Rui Li; Xingli Zhang; Tengfei Li; Caixia Jin; Wei Zou; Zhiguo Cao (Journal of Hazardous Materials, 2025)

Impact of starch morphology on the stability and color of paprika red - Yan Li; Lijun Qi; Shuangshuang Luo; Wei Gao; Taizeng Yuan; Ikram Alouk; Ruijia Zhang; Kaiyi Zou; Duoxia Xu (Journal of Food Engineering, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

Large Zn isotope variations in lower oceanic crust offer insights into oceanic crustal magma plumbing system - Wei-Qi Zhang; Chuan-Zhou Liu; Zong-Qi Zou; Xiao-Ni Li (Geochimica et Cosmochimica Acta, 2025)

Crassula perforata structured Ni3S2/NiTe electrodes enable efficient and robust seawater electrolysis at industrial-level current density - Xueling Wei; Xiangyu Zou; Qiguan Wang; Qiannan Liang; Youjun Huang; Taotao Ai; Wenhu Li; Linlin Dang; Sumin Wang (Fuel, 2025)

Highly stretchable, self-adhesive, conductive, and tough hydrogel reinforced with cellulose nanofibers for wearable biosensor and ultrasonic nanogenerator - Yijun Fu; Junyi Zou; Yijie Wang; Zhengyu Yao; Pengfei Lv; Dingsheng Wu; Qufu Wei; Wei Zhang; Yu Jiang; Dawei Li (Chemical Engineering Journal, 2025)

Microbially mediated mechanisms underlie N2O mitigation by bio-organic fertilizer in greenhouse vegetable production system - Lijun Ren; Lili Dong; Guopeng Liang; Yanyu Han; Jiaqi Li; Qingfeng Fan; Dan Wei; Hongtao Zou; Yulong Zhang (Applied Soil Ecology, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

Optimizing visible light absorption, exciton dissociation, and charge transfer through the interaction of donor-acceptor materials to enhance xanthate photodegradation - Anyang Huang; Jingyu He; Ciyuan Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Xiurong Li; Aoping He; Bingsuo Zou; et al. (Journal of Environmental Management, 2025)

Enhancing alcohol metabolism and hepatoprotection by a plant-based functional beverage in acute alcoholism and liver injury - Xinxin Zhuo; Kaizheng Zhang; Qisheng Zhang; Wei Zou; Zaixin Li; Yujie Lu; Hua Tang; Hongmei Li (Food Bioscience, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Chemical structures, antioxidant capacities, and immunostimulatory activities of pectic polysaccharides from jujube fruits collected from different producing areas - Jing Feng; Xiao Luo; Bo Li; Xiao-Yan Yang; Lin Zhang; Jing-Wei Huang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Bioscience, 2025)

Synthesis of an autochthonous microbiota responsible for the prepared process improving, flavor profile and brewing attributes of high-temperature Daqu - Hongmei Li; Yaochuan Hou; Wei Zou; Qingsong Liu; Yujie Lu; Hua Tang; Mindan Zhang; Xinxin Zhuo; Kaizheng Zhang (Food Bioscience, 2025)

Glycerol-regulated interfacial adsorption behavior of whey protein isolate for stable high internal phase emulsion gels: Impact on lipid oxidation and curcumin bioaccessibility - Jinyu Miao; Hairan Ma; Xiuying Wu; Suqiong Fang; Liqiang Zou; Mengjie Zhu; Li Ma; Wei Liu; Ruiyun Chen (Food Hydrocolloids, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Analysis of coupled wetland soil–plant ecological stoichiometric characteristics of carbon, nitrogen, and phosphorus under different disturbance intensities - Yuhan Zou; Xiying Tang; Lijuan Cui; Huazhe Li; Yinru Lei; Xinsheng Zhao; Xiajie Zhai; Jing Li; Jinzhi Wang; Rumiao Wang; Wei Li (Plant and Soil, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Magnetic field-enhanced activation of O2 by nano zero-valent iron for efficient treatment of copper-complexed wastewater - Lei Zou; Lu Wei; Yubei Liu; Mingjie Huang; Xiangling Zhang; Wenjiao Sang; Shuting Li; Chen Wang; Wei Xiang (Journal of Water Process Engineering, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

U (uranium)-polymetallic mineral systems in the world: Genetic types, metallogenic settings and ore-forming mechanisms, and perspective for exploration - Deru Xu; Chanjuan Wang; Bin Li; Guoxiang Chi; Cui Yang; Wei Deng; Wenhao Li; Ying Li; Hengsong Zhang; Longfei Luo; Yaoyao Liao; Shaohao Zou; et al. (Science China Earth Sciences, 2025)

FUT8 Regulates Cerebellar Neurogenesis and Development Through Maintaining the Level of Neural Cell Adhesion Molecule Cntn2 - Kaiyan Wei; Jinyu Zhang; Wenzheng Qu; Jinpiao Zhu; Qiang Zhu; Wen Yi; Chaochun Zou; Daqing Ma; Xuekun Li (Molecular Neurobiology, 2025)

In vitro synergistic effects of mefloquine combined with other antimicrobial agents on carbapenem-resistant Enterobacterales - Chunhong Zou; Zixin Wen; Wen Wang; Ke Gao; Shimei Shen; Lisha Shang; Xue Li; Jie Yu; Jinyi Shen; Yujin Li; Liang Chen; Jianglin Wu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Analysis of the effect of 60 Co irradiation sterilization on the chemical composition of volatile organic compounds in Rhizoma Acori Tatarinowii using GC-IMS - Man-Shu Zou; Li-Yan Xie; Wei Zhou; Yun Xiang; Chang Lei; Dan Huang (Natural Product Research, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

VvABF5 promotes ABA-mediated chlorophyll degradation by transcriptional activation of VvSGR during rachis browning of grape - Zhiqian Li; Dongfang Zou; Changjiang Nie; Xing Chen; Chang He; Xianbo Zheng; Bin Tan; Jun Cheng; Wei Wang; Pedro Martínez Gómez; Xia Ye; Jiancan Feng (Postharvest Biology and Technology, 2025)

MpYABBY2 promotes ABA accumulation and influences MpMYB11/MpbHLH79 complex to regulate anthocyanin biosynthesis in Malus ‘Pinkspire’ fruits under cold stress - Mingkun Chen; Xiaolong Liang; Yue Yang; Yu Wang; Jun Wei; Yu Duan; Haixia Peng; Ying Duan; Yuanxing Huang; Wenting Zou; Houhua Li (Postharvest Biology and Technology, 2025)

How do environmental and operational factors impact particulate matter dynamics in building construction? - Insights from real-time sensing - Xingyue Fang; Ruidong Chang; Jian Zuo; Wei Emma Zhang; Yang Zou; Kaijian Li (Journal of Environmental Management, 2025)

Lipidomic characterization of polar and non-polar lipids in egg yolk and their anti-inflammatory and analgesic activities in zebrafish - Li Wang; Cong Yin; Juanjuan Sun; Wei Li; Xiaoyan Zou; Miaojuan Zheng; Xiangheng Zeng; Haishan Zhao; Weihuan Huang; Haiyan Tian (Food Chemistry, 2025)

Transport characteristics of urban and rural aerosols based on vertical observations and deep learning predictions - Tiliang Zou; Chengzhi Xing; Jingkai Xue; Qihua Li; Wei Tan; Zehong Wu; Cheng Liu (Atmospheric Research, 2025)

Salt tolerance performance and associated gene analysis of three tilapia species (strains) - Jie Yu; Dayu Li; Jinglin Zhu; Zhiying Zou; Wei Xiao; Binglin Chen; Hong Yang (Fish Physiology and Biochemistry, 2025)

Calculating the MCI Drought Index Using Short-Term Records of High-Density Meteorological Stations: A Feasibility Study - Wenqian Zhang; Xukai Zou; Panmao Zhai; Changwen Yu; Wei Li (Journal of Meteorological Research, 2025)

Carbon dioxide–induced acidification enhances short‐lived brominated hydrocarbons production in oligotrophic oceans - Ya‐Wen Zou; Cheng‐Xuan Li; Qin‐Sheng Wei; Qian‐Yao Ma; Hui Ding; Xiao Meng Duan; Xing Zhai; Bao‐Dong Wang (Limnology and Oceanography, 2025)
Oceanic emission is a primary source of brominated very short‐lived substances (BrVSLs) to the atmosphere, which have important effects on stratospheric ozone chemistry. Marine biogeochemical processes regulating BrVSLs are often sensitive to ocean acidification. Yet, the response of BrVSLs production to acidification remains poorly understood. Herein, the effects of acidification on the production of two main BrVSLs, dibromomethane (CH 2 Br 2 ) and tribromomethane (CHBr 3 ), were studied by ship‐based incubation experiments at three stations in the South Atlantic and Indian Oceans. The average CH 2 Br 2 and CHBr 3 concentrations increased by 17.2–58.7% and 14.3–80.3% due to acidification under the in situ nutrient conditions with nutrient and/or iron limitation at the three stations, but the mechanisms driving these increases varied among different regions. The increased bromoperoxidase (BrPO) activity caused by acidification facilitated BrVSLs release in the Eastern Tropical Indian Ocean, where diatoms were dominant. CHBr 3 increased due to acidification as a result of enhanced reactivity of dissolved organic matter (DOM) in the Eastern Tropical Atlantic, where dinoflagellates were dominant. Brominated very short‐lived substances increased due to acidification as a result of a combined effect of the above two mechanisms in the Benguela Current Coastal with high phytoplankton abundance. Under the nutrient and/or iron addition conditions with nutrient and iron sufficiency, however, acidification did not promote BrVSLs production due to its only minor effect on the BrPO activity and reactivity of DOM, partly because the effect of increased oxidative stress was offset by that of changed phytoplankton composition. Our study provided a basis for future modeling on the impact of acidification on global BrVSLs emissions.

Chemosensory protein 8 confers thiamethoxam resistance in Diaphorina citri - Qian Li; Wan-Wei Hu; Ao Fang; Zhuo-Bing Wang; Xiao-Fang Yuan; Yue Sun; Zheng-Hui Zou; Nuo Chen; Tian-Xing Jing; Ying-Xue Liu; Wei Chen; Hai-Zhong Yu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Lightweight but ultrahigh-strength functionally integrated absorbers: Highly effective electromagnetic wave absorption and infrared stealth - Kejie Chen; Tianyi Hang; Wei Chen; Xin An; Yijie Zou; Yiming Chen; Jiajia Zheng; Zhaochun Li; Guoxiu Tong (Chemical Engineering Journal, 2025)

Spider silk-like strong and adhesive eutectogel fibers fabricated via a continuous spinning-polymerization process - Qian Zhang; Yan Zhang; Wei Li; Xiaowei Chen; Yonglin Jiang; Baoyi Wang; Jia Yao; Yongjia Yang; Lei Zou; Zhuo Zhao; Yafei Wang; Ying Guan; et al. (Chemical Engineering Journal, 2025)

Correlation of cyclosporine A blood concentration with kidney injury for pediatric patients after hematopoietic stem cell transplantation: a retrospective cohort study - Wei Shi; Xin Qiu; Liang Huang; Linan Zeng; Runxin Lu; Hailong Li; Kun Zou; Zhijun Jia; Guo Cheng; Qin Yu; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

FTW SERS probes with Ag NCs-GO composite structure excited by evanescent wave for in situ detection of permethrin - Pan Tao; Yang Luo; Kai Zheng; Jing Cao; Li Zhu; Xunsi Wang; Wei Zhang; Shixun Dai; Qiushun Zou; Peiqing Zhang (Analytica Chimica Acta, 2025)

Impoundment-induced stoichiometric imbalance exacerbated phosphorus limitation in a deep subtropical reservoir: Implications for eutrophication management - Hai Xu; Wei Zou; Guangwei Zhu; Yu Qiu; Huiyun Li; Mengyuan Zhu; Hans W. Paerl; Zhixu Wu; Boqiang Qin; Yunlin Zhang (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Lipidomics reveals relationship between lipid changes and the development of volatile flavor compounds in Chinese bacon during cyclic temperature smoking - Ziyi Hu; Zhaoxia Qu; Enqi He; Huiyu Zou; Zixin Li; Lei Zhou; Aihua Lou; Yan Liu; Haohua Fu; Jie Luo; Wei Quan; Qingwu Shen (Food Bioscience, 2025)

Bt toxins alter bacterial communities and their potential functions in earthworm intestines - Luyao Wang; Yixuan Fan; Lingli Zou; Lei Ge; Wei Jiang; Shengqian Chao; Beibei Lv; Kai Zhao; Jun Chen; Peng Li (Environmental Pollution, 2025)

Engineering Shewanella oneidensis to efficiently co-utilize glucose and xylose for converting cellulose hydrolysate from corn stover to electricity - Junqi Zhang; Wenjing Lv; Yangyang Wang; Jingxuan Tan; Qijing Liu; Huan Yu; Chao Li; Longhai Dai; Jing Zou; Zhanying Liu; Wen-Wei Li; Guosheng Xin; et al. (Chemical Engineering Journal, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

Innovative advanced oxidation processes based on hydrodynamic cavitation for simultaneous desulfurization and denitration - Jingang Yang; Xingda Zhao; Shiping Wei; Peihan Wang; Yundi Yang; Bo Zou; Yuanzheng Li; Liguo Song (Chemical Engineering Journal, 2025)

Contribution of PAHs and NACs to brown carbon light absorption in PM2.5 in Nanchang, Southern China - Hong Huang; Xiang Xu; Changwei Zou; Yiying Wu; Chunyi Wang; Jianlong Li; Xiang Tu; Wei Deng; Qiyuan Wang (Atmospheric Environment, 2025)

Microplastics in aquatic environments: detection, abundance, characteristics, and toxicological studies - Wei Li; Huanwei Zou; Yuguo Zheng; Guiqiang Zhang; Yujia Xiang; Dan Zhi; Yaoyu Zhou (Environmental Monitoring and Assessment, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Unilamellar MnO2 nanosheets confined Ru-clusters combined with pulse electrocatalysis for biomass electrooxidation in neutral electrolytes - Yuanqing He; Chongyang Ma; Shiheng Mo; Chung-Li Dong; Wei Chen; Shuo Chen; Huan Pang; Renzhi Ma; Shuangyin Wang; Yuqin Zou (Science Bulletin, 2025)

Enhanced removal of sulfonamide antibiotics in water using high-performance S-nZVI/BC derived from rice straw - Xiao-Ming Zou; Tiao Zhang; Yu-Hua Dong; Cui Hu; Li Yin; Yu-Ling Zheng; Mi Li; Xiao-Yu Xiao; Wei Hui (Journal of Environmental Management, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Assessing vegetation dynamics and human impacts in natural and urban areas of China: Insights from remote sensing data - Yuan Zou; Wei Chen; Siliang Li; Tiejun Wang; Le Yu; Xiao Zhang; Min Xu; Bohan Jiang; Chunying Wu; Ramesh P. Singh; Alfredo Huete; Cong-Qiang Liu (Journal of Environmental Management, 2025)

Effect of ignition timing on combustion characteristics and emissions of an X-type rotary engine with the high efficiency hybrid cycle - Run Zou; Feng Li; Jinxiang Liu; Wei Yang; Lijun Lei; Lei Zhang (Fuel, 2025)

Simultaneous detection of mixed colorants adulterated in black tea based on various morphological SERS sensors - Qingqing Cui; Jingfei Shen; Huiyan Jia; Tiehan Li; Shuci Cao; Shuai Dong; Yuming Wei; Li Zou; Yurong Chen; Yujie Wang; Jingming Ning; Luqing Li (Food Research International, 2025)

Fish freshness monitoring based on bilayer cellulose acetate/polyvinylidene fluoride membranes containing ZIF-8 loaded curcumin - Wei Wang; Jing Liang; Yuqing Wu; Wenlong Li; Xiaowei Huang; Zhihua Li; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2025)

Enhancing the physicochemical stability and bioaccessibility of curcumin-loaded soybean oil bodies emulsions in the in vitro elderly model - Wenwen Lv; Kaiyi Zou; Fengru Zhang; Yiran Jia; Ikram Alouk; Xiaoyu Li; Wei Chen; Baoguo Sun; Yanbo Wang; Duoxia Xu (Food Hydrocolloids, 2025)

The Editorial note: Electric field-driven fabrication of anisotropic hydrogels from plant proteins: Microstructure, gel performance and formation mechanism - Mengmeng Cao; Li Liao; Xingcai Zhang; Xing Chen; Shengfeng Peng; Liqiang Zou; Ruihong Liang; Wei Liu (Food Hydrocolloids, 2025)

Characterization of ornithine decarboxylase with histidine decarboxylase activity in natural histidine decarboxylase gene deletion Enterobacter hormaechei RH3 - Huijie Pei; Yilun Wang; Wei He; Yue Zhang; Lamei Yang; Jinhai Li; Yixuan Ma; Xinjie Hu; Shuhong Li; Jianlong Li; Kaidi Hu; Aiping Liu; et al. (Food Microbiology, 2025)

Rigid polymethacrylimide composites foam for efficient electromagnetic dissipation and infrared stealth - Zihang Zhang; Zixuan Wang; Yanjun Zhang; Peiyuan Zou; Mingyang Zhu; Shuangshuang Li; Xinwei Tang; Yezi Lu; Wei Li; Kaixin Lai; Wei Hong; Yufei Li; et al. (Chemical Engineering Journal, 2025)

Enhanced As(III) removal using N-chlorosulfonamide-functionalized ferrihydrite chitosan bionanocomposite hierarchical porous beads: Oxidation and adsorption - Yuanfeng Wei; Yuxin Li; Ruiying Zou; Hui Zhao; Ting wang; Yufen Xia; Zhaoshuang Li; Xinyuan Jiang; Kai Yin; Chengbin Liu (Chemical Engineering Journal, 2025)

OsWRKY49 on qAT5 positively regulates alkalinity tolerance at the germination stage in Oryza sativa L. ssp. japonica - Jingnan Cui; Shuangshuang Li; Tong Zhang; Chong Li; Yuxuan Duan; Shanbin Xu; Jingguo Wang; Hualong Liu; Luomiao Yang; Wei Xin; Yan Jia; Qingyun Bu; et al. (Theoretical and Applied Genetics, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

A comprehensive review of microplastic aging: Laboratory simulations, physicochemical properties, adsorption mechanisms, and environmental impacts - Yu Gao; Wei Gao; Yuzhi Liu; Donglei Zou; Yuan Li; Yingzi Lin; Jun Zhao (Science of The Total Environment, 2024)

Remediation of heavy metal contaminated soil in mining areas with vaterite-type biological calcium carbonate - Jun-li Chen; Chang-xiong Zou; Wei-da Wang; Chun-li Zheng; Qing-hong Jiang; Zhe Wang (Process Safety and Environmental Protection, 2024)

Investigation of stepped bottom effects on a multi-float WEC-breakwater system using OpenFOAM - Wei Peng; Xueer Yang; Qingping Zou; Jisheng Zhang; Haoran Li (Ocean Engineering, 2024)

Environmental risk control of florfenicol in water: From technology selection to mechanism discussion - Weilai Wang; Jinghan Li; Menghao Fang; Yu Chang; Tian Wang; Xinyang Wang; Haijin Liu; Wei Zou; Zhiguo Cao (Journal of Environmental Chemical Engineering, 2024)

Generation of a synthetic autochthonous microbiota responsible for the essential flavors and brewing properties of Daqu - Yujie Lu; Qin Yan; Kaizheng Zhang; Jiabin Zhang; Wei Zou; Jiangang Yang; Hongmei Li (Food Research International, 2024)

Role of Aspergillus tubingensis M16 in the quality development of instant Sichuan south-road dark tea produced by submerged fermentation - Yao Zou; Yuqing Lai; Yimiao Li; Xian Li; Chen Liu; Wei Xu (Food Bioscience, 2024)

Survival, serum biochemical parameters, hepatic antioxidant status, and gene expression of three Nile tilapia strains under pathogenic Streptococcus agalactiae challenge - Jinglin Zhu; Dayu Li; Wei Xiao; Jie Yu; Binglin Chen; Zhiying Zou; Hong Yang (Fish & Shellfish Immunology, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Instability and deformation behaviors of root-reinforced soil under constant shear stress path - Xuan Zou; Dianqing Li; Shun Wang; Shixiang Gu; Wei Wu (Engineering Geology, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Zinc isotopic composition of oceanic crust: Insights from oceanic gabbro cumulates and MORBs - Xia Wang; Zaicong Wang; Jakub Ciazela; Zongqi Zou; Wei Li; Yuanyang Yu; Ming Li; Yongsheng Liu (Chemical Geology, 2024)

Single nucleotide polymorphisms in the MRFs gene family associated with growth in Nile tilapia - Longjie Wei; Wei Xiao; Binglin Chen; Zhiying Zou; Jinglin Zhu; Dayu Li; Jie Yu; Hong Yang (Molecular Biology Reports, 2024)

Drug-Resistant Epilepsy and Gut-Brain Axis: an Overview of a New Strategy for Treatment - Shuna Chen; Yang Jiao; Chao Han; Ying Li; Wei Zou; Jing Liu (Molecular Neurobiology, 2024)

An experimental and simulated investigation into the seismic performance of Chuan-dou timber structures with infilled walls - Jie Lan; Xiaoli Li; Shuai Wang; Lan Peng; Zuyin Zou; Wei Liang; Yusheng Zeng (Bulletin of Earthquake Engineering, 2024)

Altered degree centrality and functional connectivity in girls with central precocious puberty - Zhaoxia Qin; Hang Qu; Wenlong Zou; Xiaoxia Du; Yuefeng Li; Wei Wang (Brain Imaging and Behavior, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

The viral trends and genotype diversity of norovirus in the wastewater of Shenzhen, China - Zhijiao Yue; Xiuyuan Shi; Hailong Zhang; Ziqi Wu; Chenxi Gao; Bincai Wei; Chen Du; Yuejing Peng; Xi Yang; Jing Lu; Yanpeng Cheng; Liping Zhou; et al. (Science of The Total Environment, 2024)

Effect of open-area ratios on wave attenuation over a submerged reef breakwater: An experimental study - Wei Xing; Cuiping Kuang; Hongyi Li; Jilong Chen; Lianqiang Shi; Qingping Zou (Ocean Engineering, 2024)

Flow characteristics of the rip current system adjacent to a coastal vertical structure for irregular waves - Jie Xu; Sheng Yan; Zhi-li Zou; Zhongbo Liu; Yan Wang; Cheng-shu Chang; Zhao-wei Wang; Zai-jin You (Ocean Engineering, 2024)

Fabrication, characterization, and bioactivity of self-assembled carrier-free colloidal dispersions from Citrus × Limon ‘Rosso’ essential oil and tea polyphenols - Fangying Cheng; Mianhong Chen; Zhihao Duan; Ying Zou; Yunxia He; Fanke Zeng; Yuan Yuan; Tiaokun Fu; Hao Tu; Ruyi Li; Jihua Li; Wei Zhou (Food Chemistry, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Enhanced removal of atrazine by a MoS2–Fe–BC/peroxydisulfate system: Key role of MoS2 and Fe(IV) - Xiang Li; Gaili Zhang; Yingyu Chang; Qingge Cui; Mengke Zhang; Wei Zou; Minghua Zhou (Chemical Engineering Journal, 2024)

Phytoplankton functional groups in Poyang Lake: succession and driving factors - Jinfu Liu; Haoyue Zou; Feng Deng; Yutian Liu; Wei Li; Jinying Xu; Songping Liu; Qiang Wu; Xiaoliang Zhang; Fagen Weng; Qi Huang; Hailin You; et al. (Journal of Oceanology and Limnology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Elemental and isotopic perspective on the formation of Permian mafic magmatic rocks from the Xing'an Mongolia Orogenic Belt and northern North China Craton - Wei Liu; Dongya Zou; Xiaolong Zhang; Xiaoyan Gu; Rong Xu; Gangzhu Li (Lithos, 2024)

Mechanism of aroma formation in white tea treated with solar withering - Li Zou; Caiyan Sheng; Dongzhou Xia; Jixin Zhang; Yuming Wei; Jingming Ning (Food Research International, 2024)

Dynamic changes and correlation analysis of microorganisms and flavonoids/ amino acids during white tea storage - Jianming Zhang; Wei Xin; Yiping Zou; Jingwei Yan; Wenxin Tang; Yanling Ji; Wei Li (Food Chemistry, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Rapidly reversible superwettability on textured metallic surfaces - Xianrui Zou; Yongguang Zhang; Wei Fang; Hui Jiang; Zhilu Yang; Qunyang Li; Shuilin Wu; Hongshui Wang; Donghui Wang; Huan Zhou; Tai Yang; Dan Xia; et al. (Chemical Engineering Journal, 2024)

Construction of an anti-anionic-depletion layer to mitigate the tip deposition effect for dendrite-free zinc anode - Xiaohui Li; Dan Qiu; Qiancheng Zhou; Ze Yang; Xing Zhou; Wenping Wang; Chenchen Wei; Ting Zou; Ying Yu (Chemical Engineering Journal, 2024)

Identification of LRRC46 as a novel candidate gene for high myopia - Lingxi Jiang; Chao Dai; Yao Wei; Bo Zhao; Qi Li; Zhengzheng Wu; Liang Zou; Zimeng Ye; Zhenglin Yang; Lulin Huang; Yi Shi (Science China Life Sciences, 2024)

Genetic and Pathogenic Characterization of an Iridovirus from the Cultured Largemouth Bass Micropterus salmoides - Yi-Fan Zhang; Ying Li; Peng-Tian Li; Jing Jiang; Wei-Hang Zeng; Kun Ye; Yi-Lei Wang; Peng-Fei Zou (Fishes, 2024)
The largemouth bass is a freshwater aquacultured fish species of great economic importance in China. With the rapid development of aquaculture industry and the increase in the aquaculture density of the fish, various infectious pathogens, including parasites, bacteria, and viruses, have been widely spread, which have caused huge losses to the aquaculture industry. Among them, largemouth bass iridovirus (LMBV) is one of the most harmful pathogens. In the present study, a virus strain named LMBV-GDSD was isolated from cultured largemouth bass and was successfully proliferated in FHM and EPC cells, with numerous viral particles observed in the infected cells under transmission electron microscopy analysis. The annotated complete genome of LMBV-GDSD was 99,285 bp and contained 102 ORFs. Based on genomic sequence alignment and phylogenetic analysis, the identified LMBV-GDSD belonged to the genus Ranavirus of Iridoviridae and was pathogenic to largemouth bass under regression infection experiments. In addition, the infection of LMBV-GDSD in largemouth bass could significantly up-regulate the expression of antiviral immune-related genes such as IRF3, IRF7, and Mx. It is thus providing valuable genetic data for a deeper understanding of the pathogenic mechanism of iridovirus in largemouth bass.

Microwave-assisted preparation of yellow fluorescent graphitic carbon nitride quantum dots for trace tetracycline-specific detection - Yanzhi He; Xiaopei Li; Guixiang Yao; Shuju Fang; Hang Yu; Tianru Zou; Wei Tan; Hongbin Wang (Chemosphere, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Sustainable nitrogen-doped carbons from coking wastewater and spent coffee grounds for electrocatalytic nitrate to ammonia conversion - Yaqi Zhu; Anlei Wei; Hanxiao Shi; Hao Hu; Kanrong Tang; Nan Li; Jirui Zou (Journal of Environmental Chemical Engineering, 2024)

The improvement of water barrier property in gelatin/carboxymethyl cellulose composite film by electrostatic interaction regulation and its application in strawberry preservation - Kaibo Yu; Lei Zhou; Hairong Huang; Jing Xu; Yangyang Li; Wenzhi Yu; Shengfeng Peng; Liqiang Zou; Wei Liu (Food Chemistry, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

SfuPKS2, a novel type III polyketide synthase from Sargassum fusiforme, shows high substrate specificity - Jia-Min Xu; Yi-Cheng Xu; Chen-Xi Cheng; Dong-Sheng Zhao; Zhi-Wei Hu; Shu-Ming Li; Salah Fatouh Abou-Elwafa; Xiufeng Yan; Hui-Xi Zou; Nan Li (Journal of Applied Phycology, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

The Role of Histone H2B Acetylation Modification in Aluminum-Induced Cognitive Dysfunction - Jie Gao; Wei Liu; Jing Pei; Jing Li; Niping Hao; Shuo Yang; Xiaoming Yang; Danfeng Zou; Kebin Xu; Lifeng Zhang (Biological Trace Element Research, 2024)

Can habitual tea drinking be an effective approach against age-related neurodegenerative cognitive disorders: A systematic review and meta-analysis of epidemiological evidence - Wei Quan; Yong Lin; Huiyu Zou; Maiquan Li; Jie Luo; Zhiyong He; Jie Chen; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Triterpenoids from the leaves of Eleutherococcus sessiliflorus, and their antiproliferative activities in TNF-α induced HFLS-RA cells - Yan Liu; Yuqing Wang; Peng Jiang; Dong Han; Jiatong Wu; Siyi Wang; Haidan Zou; Yikai Jiang; Xiaomao Li; Juan Pan; Zhichao Hao; Wei Guan; et al. (Phytochemistry, 2024)

Catalytic removal of chemical oxygen demand during ozonation of the simulated wastewater from coal chemical industry - Hai-Xu Zou; Yang-Yang Xu; Xing Fan; Feng-Yun Ma; Wei-Dong Cao; De-Quan Li; Jia-Feng Song (Journal of Water Process Engineering, 2024)

Nitrate sources and transformations in a river-reservoir system: Response to extreme flooding and various land use - Xingchen Zhao; Hai Xu; Lijuan Kang; Guangwei Zhu; Hans W. Paerl; Huiyun Li; Mingliang Liu; Mengyuan Zhu; Wei Zou; Boqiang Qin; Yunlin Zhang (Journal of Hydrology, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Potential structure–function relationships of pectic polysaccharides from quinoa microgreens: Impact of various esterification degrees - Jie Li; Jing Feng; Xiao Luo; Mei-Mei Qu Mo; Wen-Bing Li; Jing-Wei Huang; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Research International, 2024)

Ultra-trace Ag doped carbon quantum dots with peroxidase-like activity for the colorimetric detection of glucose - Wei Tan; Guixiang Yao; Hang Yu; Yanzhi He; Mingrong Lu; Tianru Zou; Xiaopei Li; Pengyuan Yin; Pei Na; Wenrong Yang; Min Yang; Hongbin Wang (Food Chemistry, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

Novel seamless shell-core microbead for probiotics encapsulation: Influence of gel structure on storage stability and gastrointestinal activity - Hongxia Gao; Youfa Xie; Ziling Li; Chunqing Bai; Liqiang Zou; Wei Liu (Food Hydrocolloids, 2024)

Bridging the buried interface with conjugated molecule for highly efficient carbon-based inorganic CsPbI2Br perovskite solar cells fabricated in air - Yifei Shi; Lei Zhang; Shuming Hu; Xu Wang; Jiajia Han; Jincheng Huang; Junjie Chen; Yuanfang Zhang; Xinlong Zhang; Jintao He; Hengzhi Zuo; Jiayao Ju; et al. (Chemical Engineering Journal, 2024)

The effect of extracellular polymeric substances on MICP solidifying rare earth slags and stabilizing Th and U - Chang-xiong Zou; Zhen-bo Sun; Wei-da Wang; Tan Wang; Yan-xin Bo; Zhe Wang; Chun-li Zheng (World Journal of Microbiology and Biotechnology, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Comparative study on inhibitory effects of ginsenosides on human pancreatic lipase and porcine pancreatic lipase: structure-activity relationships and inhibitory mechanism - An-Qi Wang; Ya-Jie Wang; Jing Zhang; Yi-Ming Fan; Shi-Yang Li; Li-Wei Zou (Natural Product Research, 2024)

Oxymatrine induces apoptosis in non-small cell lung cancer cells by downregulating TRIM46 - Yi Zhong; Biaobiao Luo; Min Hong; Sheng Hu; Dian Zou; Yang Yang; Shaozhong Wei; Mohammad Omar Faruque; Shuang Dong; Xianmin Zhu; Xiaoyu Li; Yuanxiang Li; et al. (Toxicon, 2024)

Fourteen undescribed steroidal saponins from Solanum capsicoides leaves and their neuroprotective effects - Yan Liu; Xin-Yuan Li; Jia-tong Wu; Han Wang; Xin Meng; Hai-Dan Zou; Juan Pan; Wei Guan; Adnan Mohammed Algradi; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Acute exposure to tris(2,4-di-tert-butylphenyl)phosphate elicits cardiotoxicity in zebrafish (Danio rerio) larvae via inducing ferroptosis - Xingli Zhang; Jing Shi; Ruonan Wang; Junguo Ma; Xiaokang Li; Wenwen Cai; Tengfei Li; Wei Zou (Journal of Hazardous Materials, 2024)

Recombinase polymerase amplification combined with Pyrococcus furiosus Argonaute for fast Salmonella spp. testing in food safety - Liyun Lin; Qiulan Luo; Liejun Li; Yuzhong Zheng; Huagui Wei; Jiayu Liao; Yaqun Liu; Mouquan Liu; Zhonghe Wang; Wanling Lin; Xianghui Zou; Hui Zhu; et al. (International Journal of Food Microbiology, 2024)

Acceleration of the charge transfer rate for efficient photocatalytic hydrogen production via adjusting modulator and introducing electronic bridge dual strategies - Xingyan Liu; Haibo Zhou; Ruolan Li; Maosen Xu; Chenghua Zhang; Zhengsijia Wu; Youzhou He; Xu Zou; Min Fu; Siping Wei (Fuel, 2024)

C–C bond coupling differences between β-O-4 and 4-O-5 ether bonds over hydrophobic mesoporous Ru/MY-O catalysts: from lignin model compounds to polycyclic alkanes - Zhuang Li; Zi-Chun Fan; Xiang Bai; Xian-Yong Wei; Yierxiati. Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Jun-Long Wang; Xing Fan; Xiao-Yan He; Hai-Xu Zou; et al. (Fuel, 2024)

Reuterin formed by poultry-derived Limosilactobacillus reuteri HLRE05 inhibits the growth of enterotoxigenic Bacillus cereus in in vitro and fermented milk - Xinrui Li; Yijuan Li; Ke Zhu; Kaixiang Zou; Yuxin Lei; Chengwei Liu; Hua Wei; Zhihong Zhang (Food Bioscience, 2024)

Phosphorus fertilizer management for high yields in intensive winter wheat-summer maize rotation system: Integrating phosphorus budget and soil available phosphorus - Shunjin Li; Xiuxiu Chen; Zikai Wang; Dongxun Wu; Meng Wang; Torsten Müeller; Chunqin Zou; Xinping Chen; Wei Zhang (Field Crops Research, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Electrospun PAN/BaTiO3/MXene nanofibrous membrane with significantly improved piezoelectric property for self-powered wearable sensor - Yijun Fu; Jiahao Liu; Junyi Zou; Sijun Xu; Yanhong Wei; Wei Zhang; Dawei Li (Chemical Engineering Journal, 2024)

Using rice straw-augmented ecological floating beds to enhance nitrogen removal in carbon-limited wastewater - Xixi Cai; Jianying Li; Haoping Wu; Siyu Yang; Yi You; Dunhai Li; Wei Xing; Chunping Zou; Xiaoyu Guo; Jibing Li; Hongjie Qin (Bioresource Technology, 2024)

Hybrid origin and hybrid status of the endangered Ilex sanqingshanensis revealed by molecular and morphological evidence - Wei-li Liu; Dan-qi Li; Yi-ping Zou; Ming-zhuo Hao; Zhi-yong Zhang; Deng-mei Fan; Yi Yang (Plant Systematics and Evolution, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

Interactions of monolayer molybdenum disulfide sheets with metalloid antimony in aquatic environment: Adsorption, transformation, and joint toxicity - Wei Zou; Yu Zhang; Xingli Zhang; Guoqing Zhang; Xiaokang Li; Caixia Jin; Zhiguo Cao (Science of The Total Environment, 2024)

Subtypes of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Wei-Lan Yan; Xiao-Man Li; Si-Yuan Qin; Nian-Yu Xue; Yang Zou; Jing-Hao Li; Xiao-Xuan Zhang; Hong-Bo Ni (Research in Veterinary Science, 2024)

The bZIP transcription factor MpbZIP9 regulates anthocyanin biosynthesis in Malus ‘Pinkspire’ fruit - Mingkun Chen; Xiaoyun Cao; Yuanxing Huang; Wenting Zou; Xiaolong Liang; Yue Yang; Yu Wang; Jun Wei; Houhua Li (Plant Science, 2024)

Control of tobacco-specific nitrosamines by the Bacillus siamensis: Strain isolation, genome sequencing, mechanism analysis and genetic engineering - Xinyu Dong; Jun Yu; Changwen Ye; Dandan Liu; Dian Zou; Zhenying Han; Qingru Yu; Kuo Huang; Hao Li; Xuetuan Wei (Journal of Hazardous Materials, 2024)

Imidazole-linked covalent organic polymers with abundant oxygen and nitrogen active centers for advanced aqueous zinc-organic batteries - Yongyao Liu; Zhonglin Li; Chengliang Li; Yifan Wei; Shuai Yan; Zhenyu Ji; Shuixiang Zou; Hengbo Li; Yuanzheng Liu; Cheng Chen; Xiang He; Mingyan Wu (Chemical Engineering Journal, 2024)

Facile fabrication of 3D Janus foams of electrospun cellulose nanofibers/rGO for high efficiency solar interface evaporation - Zengyan Sui; Xiaolin Xue; Qunhao Wang; Mei Li; Yuefei Zou; Wei Zhang; Canhui Lu (Carbohydrate Polymers, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

Two new chromone derivatives from the rhizosphere soil fungus Ilyonectria robusta - Min Kuang; Wei-Wei Peng; Yuan-Tao Huang; Mei-Fang Li; Si-Yu Qin; Yu-Ting Zheng; Li Xu; Qi Huang; Zhen-Xing Zou (Natural Product Research, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Atom-by-atom optimizing the surface termination of Fe-Pt intermetallic catalysts for alkaline hydrogen evolution reaction - Qing Liang; Fanling Meng; Wenwen Li; Xu Zou; Kexin Song; Xin Ge; Zhou Jiang; Yuhua Liu; Meiqi Liu; Zhenyu Li; Taowen Dong; Zhongjun Chen; et al. (Science Bulletin, 2024)

Combination of chemometrics and mass spectrometric methods for the data mining of molecular structure information of coal and biomass - Guo-Sheng Li; Xing Bai; Min-Hua Wang; Xing Fan; Xiao-Yan He; Yierxiati Dilixiati; Xian-Yong Wei; Hai-Xu Zou; Guligena Pidamaimaiti (Fuel, 2024)

A tale of lockdown policies on the transmission of COVID-19 within and between Chinese cities: A study based on heterogeneous treatment effect - Jingjing Li; Chu Zhuang; Wei Zou (Economics & Human Biology, 2024)

Rational synthesis of 1,3,4-thiadiazole based ESIPT-fluorescent probe for detection of Cu2+ and H2S in herbs, wine and fruits - Yu Sun; Jie Mu; Yongchen Wang; Chengwei Lü; Li-Wei Zou (Analytica Chimica Acta, 2024)

Deciphering solute transport, microbiota assembly patterns and metabolic functions in the hyporheic zone of an effluent-dominated river - Longfei Wang; Ziyi Wang; Yi Li; Wei Cai; Yina Zou; Cizhang Hui (Water Research, 2024)

Observations of HONO and its precursors between urban and its surrounding agricultural fields: The vertical transports, sources and contribution to OH - Chengzhi Xing; Cheng Liu; Qihua Li; Shanshan Wang; Wei Tan; Tiliang Zou; Zhuang Wang; Chuan Lu (Science of The Total Environment, 2024)

Toxicity of hexagonal boron nitride nanosheets to freshwater algae: Phospholipid membrane damage and carbon assimilation inhibition - Wei Zou; Yuhan Huo; Xingli Zhang; Caixia Jin; Xiaokang Li; Zhiguo Cao (Journal of Hazardous Materials, 2024)

Revealing discrepancies and drivers in the impact of lomefloxacin on groundwater denitrification throughout microbial community growth and succession - Hua Zou; Jiangtao He; Yanjia Chu; Baoshi Xu; Wei Li; Shiwen Huang; Xiangyu Guan; Fei Liu; Haiyan Li (Journal of Hazardous Materials, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Identification and molecular mechanism of novel bifunctional peptides from Duroc × (Landrace × Yorkshire) pig dry-cured ham: A peptidomics and in silico analysis - Daodian Wang; Guangqiang Wei; Yanying Yang; Yanling Zou; Xiang Li; Yanan Shi; Aixiang Huang (Food Research International, 2024)

Circular RNA circRest regulates manganese induced cell apoptosis by targeting the mmu-miR-6914–5p/Ephb3 axis - Wenmin Lu; Jiacheng He; Shengtao Wei; Chuanqiao Tang; Xiaoli Ma; Danni Li; Hao Chen; Yunfeng Zou (Environmental Pollution, 2024)

Prediction of phthalate in dust in children's bedroom based on gradient boosting regression tree - Chanjuan Sun; Qinghao Wang; Jialing Zhang; Wei Liu; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Qihong Deng; Xin Zhang; Hua Qian; Zhijun Zou; Xu Yang; et al. (Building and Environment, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Characterization of glucose metabolism in high-growth performance Nile tilapia (Oreochromis niloticus) - Binglin Chen; Wei Xiao; Dayu Li; Zhiying Zou; Jinglin Zhu; Jie Yu; Hong Yang (Aquaculture, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Evidence for partial melting and earthquake activity in the crust from a 2-D electrical resistivity model in the vicinity of the Chayu region, southeastern Jiali-Chayu fault, Tibetan Plateau - Weiqiang Li; Changqing Yu; Changchun Zou; Dingbang Wei; Huimin Zhang; Xiangzhi Zeng; Pengxiao Fan; Chenggong Liu (Tectonophysics, 2024)

Carbon reduction measures-based life cycle assessment of the photovoltaic-supported sewage treatment system - Jiahong Guo; Wei Zhang; Jing Zhang; Lingzhi Xie; Xiding Zeng; Jianmei Zhong; Oufan Zhao; Kun Yang; Zhangyu Li; Ruiwen Zou; Zepu Bai; Qing Wang; et al. (Sustainable Cities and Society, 2024)

Removal of bisphenol A in a heterogeneous Fenton system via biochar synthesized using different Fe precursors: Properties, effects, and mechanisms - Xiang Li; Gaili Zhang; Yan Jia; Wei Zou; Guoqing Zhang; Yuwei Pan; Minghua Zhou (Science of The Total Environment, 2024)

A ratiometric fluorescence amine sensor based on carbon quantum dot-loaded electrospun polyvinylidene fluoride film for visual monitoring of food freshness - Wenjun Song; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Yuhong Xue; Yue Sun; Wei Sun; Junjun Zhang; Xiaowei Huang; Zhihua Li; Tingting Shen; Yanxiao Li; et al. (Food Chemistry, 2024)

Manganese-induced neurological pyroptosis: Unveiling the mechanism through the ROS activaed Caspase-3/GSDME signaling pathway - Jiacheng He; Xiaoli Ma; Jie Zhang; Yi-ping Yang; Huiyan Qin; Hao Chen; Shengtao Wei; Fangfei Li; Jian Wang; Guiqiang Liang; Yunfeng Zou (Food and Chemical Toxicology, 2024)

Dynamic stability and frequency responses of the tilted curved nanopipes in a supersonic airflow via 2D hybrid nonlocal strain gradient theory - Jinzhi Yin; Yunhe Zou; Jianfeng Li; Wei Zhang; Xiyue Li; Mostafa Habibi (Engineering Structures, 2024)

Contrasting Cu isotopes in mid-ocean ridge basalts and lower oceanic crust: Insights into the oceanic crustal magma plumbing systems - Zongqi Zou; Zaicong Wang; Yi-Gang Xu; Jakub Ciazela; Xia Wang; Stephen Foley; Wei-Qi Zhang; Wei Li; Ming Li; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Revealing the roles of biochar derived from iron-rich fermented sludge residue in anaerobic digestion - Hong-Yu Jin; Zhang-Wei He; Yong-Xiang Ren; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Conjugated Linoleic Acid Reduces Lipid Accumulation via Down-regulation Expression of Lipogenic Genes and Up-regulation of Apoptotic Genes in Grass Carp (Ctenopharyngodon idella) Adipocyte In Vitro - Hua Yu; Zhao-xia Zou; Wei Wei; Ying Li (Marine Biotechnology, 2024)

Properties and mechanisms of steel slag strengthening microbial cementation of cyanide tailings - Chang-xiong Zou; Meng Xiao; Qing-hong Jiang; Zhe Wang; Chun-li Zheng; Wei-da Wang (Chemosphere, 2024)

Length-based stock assessment for Procambarus clarkii aquaculture management in China: An alarming of ongoing recruitment overfishing - Shiyu Jin; Yubin Jiao; Junru Li; Zhiqiang Xu; Yu Xu; Mengmei Zou; Jun Ding; Xiangqian Li; Zhaoyu Wang; Meng Wang; Wei Li; Tanglin Zhang; et al. (Aquaculture, 2024)

Redox gradients drive microbial community assembly patterns and molecular ecological networks in the hyporheic zone of effluent-dominated rivers - Yuming Wang; Yutao Wang; Jiahui Shang; Longfei Wang; Yi Li; Ziyi Wang; Yina Zou; Wei Cai; Linqiong Wang (Water Research, 2024)

Study on Airflow Distribution and Energy Conservation in a BSL-4 Laboratory Involved in Aerosol Infection Risk - Jianmei Zhong; Wei Zhang; Xiaoli Wang; Jinsheng Zhan; Tao Xia; Lingzhi Xie; Xiding Zeng; Kun Yang; Zhangyu Li; Ruiwen Zou; Zepu Bai; Qing Wang; et al. (Sustainable Cities and Society, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

A SERS aptasensor based on a flexible substrate for interference-free detection of carbendazim in apple - Xiaoou Wei; Wenjun Song; Yushan Fan; Yue Sun; Zhihua Li; Shiqi Chen; Jiyong Shi; Di Zhang; Xiaobo Zou; Xuechao Xu (Food Chemistry, 2024)

Effect of aqueous extract of Millettia speciosa Champ on intestinal health maintenance and immune enhancement of Cyprinus carpio - Qingshi Chen; Tianli Wei; Min Li; Shulin Liu; Jinxia Wu; Guohuan Xu; Jixing Zou; Shaolin Xie (Fish & Shellfish Immunology, 2024)

Microscopic hyperspectral imaging and an improved detection model based detection of Mycogone perniciosa chlamydospore in soil - Xuan Wei; Yongjie Liu; Qiming Song; Jinping Zou; Zhiqiang Wen; Jiayu Li; Dengfei Jie (European Journal of Agronomy, 2024)

Predicting peak deviatoric stress of gravels with a novel segmented feature transformation approach - Duo Li; Degao Zou; Jingmao Liu; Kaiyuan Xu; Fanwei Ning; Zhenggang Zhan; Wei Jin (Computers and Geotechnics, 2024)

Microplastic and Silica Colloid Transport in a Saturated Porous Medium Under Various Flow Directions: the Effect of Gravity - Dan Xiao; Shiwei Li; Zhen Chen; Shubin Zou; Wahyunanto Agung Nugroho; Mingxin Huo; Dongmei Zhang; Wei Fan (Water, Air, & Soil Pollution, 2024)

Genetic diversity assessment for reintroduced Przewalski’s horse (Equus ferus) based on newly developed SSR markers - Lijiao Zhang; Gang Sun; Entemahan Azhanhan; Yan Li; Wei Shi; Dahu Zou; Hefan Zhang; Jiajia Ding; Mimi Kessler; Muyang Wang; Weikang Yang (Conservation Genetics Resources, 2023)

City-level decoupling between livestock and crop production and its effect on fertilizer usage: Evidence from China - Xiang Kang; Mingxi Du; Qiuyu Liu; Haifeng Du; Wei Zou; Li Zhao; Yulong Yin; Zhenling Cui (Science of The Total Environment, 2023)

Analysis of spatial structure and filling mechanism of a paleokarst channel against a background of denudation: A case study in the Tahe Oilfield, Tarim basin - Chenhe Zhang; Zhiqian Gao; Tailiang Fan; Debin Yang; Duan Wei; Jun Wu; Jinxian Liu; Huitao Zhang; Xinlei Zhang; Bo Li; Zhe Chang; Yu Gu; et al. (Marine and Petroleum Geology, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Mixed B-site driven [InBr4]− tetrahedral efficient blue emission - Tongzhou Li; Tao Huang; Qilin Wei; Wenchao Lin; Xiaoyan Lu; Xiaodong Shen; Shichao Zhou; Weizheng Liang; Bingsuo Zou (Chemical Engineering Journal, 2023)

Well-constructed a water stable Cu-BTC@TpPa-1 binary composite with excellent capture ability toward malachite green - Jiaying Zou; Yan Li; Haotian Dong; Na Ma; Wei Dai (Environmental Science and Pollution Research, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

Ag/TiO2 nanohybrids induce fibrosis-related epithelial-mesenchymal transition in lung epithelial cells and the influences of silver content and silver particle size - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Lingyue Zou; Changcun Bai; Yongshuai Yao; Zhihui Wang; Yuying Xue; Tianshu Wu; Ting Zhang; Meng Tang (Science of The Total Environment, 2023)

Gastrointestinal microbiome, resistance genes, and risk assessment of heavy metals in wild giant pandas - Lei Jin; Hongning Wu; Guo Li; Shengzhi Yang; Rongping Wei; Yan Huang; Petri Penttinen; Wenwen Deng; Jianbin Chen; Xinfeng Han; Caiwu Li; Lan Hu; et al. (Science of The Total Environment, 2023)

Solidification treatment of rare earth tailings by a renewable biological cementation method - Wei-da Wang; Tan Wang; Zhen-bo Sun; Yan-xin Bo; Chang-xiong Zou; Zhe Wang; Chun-li Zheng (Process Safety and Environmental Protection, 2023)

An intracellular transporter OsNRAMP7 is required for distribution and accumulation of iron into rice grains - Jingjun Li; Yuanyuan Liu; Linghui Kong; Ending Xu; Yu Zou; Peijiang Zhang; Wei Zhang; Xi Chen (Plant Science, 2023)

Contribution identification of hydrolyzed products of potassium ferrate on promoting short-chain fatty acids production from waste activated sludge - Cong-Cong Tang; Min Zhang; Bo Wang; Zheng-Shuo Zou; Xing-Ye Yao; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Aijie Wang; Zhang-Wei He (Journal of Environmental Management, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Comparative transcriptomes reveal different tolerance mechanisms to Streptococcus agalactiae in hybrid tilapia, nile tilapia, and blue tilapia - Jinglin Zhu; Zhiying Zou; Dayu Li; Wei Xiao; Jie Yu; Binglin Chen; Hong Yang (Fish & Shellfish Immunology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Genome-wide identification and analysis of the evolution and expression pattern of the SBP gene family in two Chimonanthus species - Ge-Ge Jiang; Qian-Qian Wan; Wei Zou; Gui-Ting Hu; Li-Yuan Yang; Li Zhu; Hui-Juan Ning (Molecular Biology Reports, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

In situ microwave-assisted preparation of NS-codoped carbon dots stabilized silver nanoparticles as an off-on fluorescent probe for trace Hg2+ detection - Pengyuan Yin; Tianru Zou; Guixiang Yao; Shaoqing Li; Yanzhi He; Guizhen Li; Da Li; Wei Tan; Min Yang (Chemosphere, 2023)

Highly photoluminescent tryptophan-coated copper nanoclusters based turn-off fluorescent probe for determination of tetracyclines - Tianru Zou; Shaoqing Li; Guixiang Yao; Rui Qu; Wenrong Yang; Hongbin Wang; Wei Tan; Min Yang (Chemosphere, 2023)

A rapid segmentation method for weed based on CDM and ExG index - Xiaowu Han; Han Wang; Ting Yuan; Kunlin Zou; Qianfeng Liao; Kai Deng; Zhiqin Zhang; Chunlong Zhang; Wei Li (Crop Protection, 2023)

Configured quantum reservoir computing for multi-task machine learning - Wei Xia; Jie Zou; Xingze Qiu; Feng Chen; Bing Zhu; Chunhe Li; Dong-Ling Deng; Xiaopeng Li (Science Bulletin, 2023)

Differential developmental and proinflammatory responses of zebrafish embryo to repetitive exposure of biodigested polyamide and polystyrene microplastics - Xingli Zhang; Jing Shi; Peng Yuan; Tengfei Li; Zhiguo Cao; Wei Zou (Journal of Hazardous Materials, 2023)

Revealing methane production potential from waste activated sludge through citric acid-assisted hydrogen corrosion of zero valent iron - Fei Wang; Zheng-Shuo Zou; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2023)

Neonatal-Onset Inflammatory Tinea Capitis by Microsporum canis Due to a Woolen Hat - Xueke Zou; Wei Chen; Ruoyu Li (Mycopathologia, 2023)

Time-lag effects of flood stimulation on methane emissions in the Dongting Lake floodplain, China - Tao Wang; Zhengmiao Deng; Yonghong Xie; Buqing Wang; Shaoan Wu; Feng Li; Wei Wang; Yeai Zou; Xu Li; Zhiyong Hou; Jing Zeng; Mei Wang; et al. (Agricultural and Forest Meteorology, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

The association between maternal air pollution exposure and the incidence of congenital heart diseases in children: A systematic review and meta-analysis - Xiaoyu Wan; Sixuan Wei; Yaqi Wang; Jun Jiang; Xinyao Lian; Zhiyong Zou; Jing Li (Science of The Total Environment, 2023)

Enhanced organic pollutant removal in saline wastewater by a tripolyphosphate-Fe0/H2O2 system: Key role of tripolyphosphate and reactive oxygen species generation - Xiang Li; Huajing Song; Gaili Zhang; Wei Zou; Zhiguo Cao; Yuwei Pan; Guoqing Zhang; Minghua Zhou (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Seismogenic structure of the 2020 Jiashi, Xinjiang Ms 5.4 and Ms 6.4 moderate earthquakes - Shan-Shan Liang; Guang-Wei Zhang; Xiao-Ning Huang; Li-Ye Zou; Yan-Qiong Liu; Yun-Da Ji (Applied Geophysics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

A cell-based electrochemical taste sensor for detection of Hydroxy-α-sanshool - Mengyu Hao; Zhihua Li; Xiaowei Huang; Yuan Wang; Xiaoou Wei; Xiaobo Zou; Jiyong Shi; Zhangqi Huang; Litao Yin; Liying Gao; Yanxiao Li; Melvin Holmes; et al. (Food Chemistry, 2023)

Effects of Lycium barbarum on gluten structure, in vitro starch digestibility, and compound noodle quality - Fei Hu; Jin-Yu Li; Peng-Ren Zou; Kiran Thakur; Jian-Guo Zhang; Mohammad Rizwan Khan; Zhao-Jun Wei (Food Bioscience, 2023)

The controlled degradation of bacterial cellulose in simulated physiological environment by immobilization and release of cellulase - Guodong Liu; Faxing Zou; Wei He; Junfei Li; Yajie Xie; Mengjiao Ma; Yudong Zheng (Carbohydrate Polymers, 2023)

Cellulose sulfate lithium as a conductive binder for LiFePO4 cathode with long cycle life - Xu Su; Han Fang; Hao Yang; Fangfang Zou; Gang Li; Lian Wang; Hongxin Liao; Wei Guan; Xuebu Hu (Carbohydrate Polymers, 2023)

A systematic characterization of soil/dust ingestion for typical subpopulations in China - Na Li; Jie Zhang; Hao Yu; Menghan Xu; Qian Feng; Jiayi Zhang; Xiaoyu Wang; Pengkun Wei; Yujuan Fan; Guangxuan Yan; Wei Zou; Zhiguo Cao; et al. (Environmental Geochemistry and Health, 2023)

Indoor air quality and its health effects in offices and school buildings in the Yangtze River Delta - Chanjuan Sun; Jingyu Chen; Shijie Hong; Yinping Zhang; Haidong Kan; Zhuohui Zhao; Furong Deng; Xiangang Zeng; Yuexia Sun; Hua Qian; Wei Liu; Jinhan Mo; et al. (Air Quality, Atmosphere & Health, 2023)

Rainstorm events trigger algal blooms in a large oligotrophic reservoir - Pengcheng Shi; Mengyuan Zhu; Rifu You; Huiyun Li; Wei Zou; Hai Xu; Man Xiao; Guangwei Zhu (Journal of Hydrology, 2023)

Microbial community composition and cooccurrence patterns driven by co-contamination of arsenic and antimony in antimony-mining area - Wei-song Pan; Qi Zou; Min Hu; Wai-chin Li; Xiao-ran Xiong; Yan-ting Qi; Chuan Wu (Journal of Hazardous Materials, 2023)

Effects of α-Fe2O3 nanoparticles and biochar on plant growth and fruit quality of muskmelon under cadmium stress - Yunqiang Wang; Ying Zhou; Yan Guan; Zhengkang Zou; Zhengming Qiu; Zhaoyi Dai; Licong Yi; Wei Zhou; Junli Li (Environmental Geochemistry and Health, 2023)

Methods and assessments of two-way time synchronization based on BDS-3 Ka-band satellite-ground link observations - Yanming Guo; Yan Bai; Jian Zhang; Wei Li; Decai Zou; Shuaihe Gao; Haibo Yuan; Yuping Gao; Xiaochun Lu (GPS Solutions, 2023)

A visual bi-layer indicator based on mulberry anthocyanins with high stability for monitoring Chinese mitten crab freshness - Xiaowei Huang; Liuzi Du; Zhihua Li; Jin Xue; Jiyong Shi; Haroon Elrasheid Tahir; Xiaodong Zhai; Junjun Zhang; Ning Zhang; Wei Sun; Xiaobo Zou (Food Chemistry, 2023)

Indolocarbazole-based deep-blue multiple-resonance narrowband emitters and efficient organic light-emitting diodes - Qinqin Peng; Wei Yang; Nengquan Li; Shaolong Gong; Xiang Gao; Changqing Ye; Yang Zou; Chuluo Yang (Chemical Engineering Journal, 2023)

Recent advances and perspectives in roles of humic acid in anaerobic digestion of waste activated sludge - Zhang-Wei He; Fei Wang; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2023)

From bench to bedside: targeting lymphocyte activation gene 3 as a therapeutic strategy for autoimmune diseases - Xueyin Zhou; Yiming Gu; Huihong Wang; Wei Zhou; Lei Zou; Shuting Li; Chunyan Hua; Sheng Gao (Inflammation Research, 2023)

Enhanced nitrogen removal via biochar-mediated nitrification, denitrification, and electron transfer in constructed wetland microcosms - Xuan Guo; Huimin Xie; Weiliang Pan; Peng Li; Lianfeng Du; Guoyuan Zou; Dan Wei (Environmental Science and Pollution Research, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Spatiotemporal variability in extreme precipitation and associated large-scale climate mechanisms in Central Asia from 1950 to 2019 - Wei Wei; Shan Zou; Weili Duan; Yaning Chen; Shuai Li; Yiqi Zhou (Journal of Hydrology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Polyacrylonitrile fibers network reinforced polymer electrolyte with Li-Sn alloy layer protected Li anode toward ultra-long cycle lifespan for room-temperature solid-state batteries - Yuanyuan Zhang; Hongyi Wang; Yuqi Yang; Jia Xie; Qijiu Deng; Wei Zou; Aijun Zhou; Jingze Li (Chemical Engineering Journal, 2023)

Effects of different rapid cooling temperatures and annealing on functional properties of starch straws after thermoplastic extrusion - Kun Wang; Feixue Zou; Haiteng Tao; Wei Gao; Li Guo; Bo Cui; Chao Yuan; Pengfei Liu; Lu Lu; Zhengzong Wu (Carbohydrate Polymers, 2023)

A novel 4-O-endosulfatase with high potential for the structure-function studies of chondroitin sulfate/dermatan sulfate - Lin Wei; Yingying Xu; Min Du; Ying Fan; Ruyi Zou; Xiangyu Xu; Qingdong Zhang; Yu-Zhong Zhang; Wenshuang Wang; Fuchuan Li (Carbohydrate Polymers, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

One-stop rapid decomplexation and copper capture of Cu(II)-EDTA with nanoscale zero valent iron - Xingyue Zou; Yuhang Zhang; Kai Wei; Jie Dai; Chengliang Mao; Lufa Hu; Hao Li; Yancai Yao; Lizhi Zhang (Journal of Hazardous Materials, 2023)

Facile synthesis of acid catalyzed sulfonic acid-amide functionalized magnetic sodium alginate and its efficient adsorption for ciprofloxacin and moxifloxacin - Junyi Jiang; Xincheng Jiang; Yuhong Zou; Jun Zhai; Wei Ding; Hong Li; Huaili Zheng (Journal of Cleaner Production, 2023)

Combine thermal processing with polyvalent phage LPEK22 to prevent the Escherichia coli and Salmonella enterica contamination in food - Yue Zhang; Geng Zou; Md. Sharifull Islam; Kun Liu; Suqiang Xue; Zhiyong Song; Yingwang Ye; Yang Zhou; Yuanguo Shi; Shaozhong Wei; Rui Zhou; Huanchun Chen; et al. (Food Research International, 2023)

Electric field-driven fabrication of anisotropic hydrogels from plant proteins: Microstructure, gel performance and formation mechanism - Mengmeng Cao; Li Liao; Xingcai Zhang; Xing Chen; Shengfeng Peng; Liqiang Zou; Ruihong Liang; Wei Liu (Food Hydrocolloids, 2023)

Rapid detection of Staphylococcus aureus in food safety using an RPA-CRISPR-Cas12a assay - Liyun Lin; Guangcai Zha; Huagui Wei; Yuzhong Zheng; Peikui Yang; Yaqun Liu; Mouquan Liu; Zhonghe Wang; Xianghui Zou; Hui Zhu; Qiulan Luo; JinQuan Li; et al. (Food Control, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

The Menyuan, Qinghai MS6.9 Earthquake on January 8, 2022: A Strike-slip Cascading Rupture Event - Liang Shan-shan; Xu Zhi-guo; Zhang Guang-wei; Shi Jian-yu; Zou Li-ye (Pure and Applied Geophysics, 2023)

Soil particle size fractions affect arsenic (As) release and speciation: Insights into dissolved organic matter and functional genes - Qi Zou; Hang Wei; Zhiliang Chen; Ping Ye; Jianqiang Zhang; Mengqiang Sun; Ling Huang; Jing Li (Journal of Hazardous Materials, 2023)

A residual convolutional neural network with multi-block for appliance recognition in non-intrusive load identification - Leitao Qu; Yaguang Kong; Meng Li; Wei Dong; Fan Zhang; Hongbo Zou (Energy and Buildings, 2023)

Quantity or quality: Environmental legislation and corporate green innovations - Xiaoqi Huang; Wei Liu; Zhan Zhang; Xinyu Zou; Pujuan Li (Ecological Economics, 2023)

Flexible quasi-3D zinc ion microcapacitor based on V2O5-PANI cathode and MXene anode - Ao Li; Zhichao Wei; Yongxin Wang; Yuhang Zhang; Mengjie Wang; Hongyun Zhang; Yanan Ma; Chenxu Liu; Junjie Zou; Binghui Ge; Feng Cheng; Yang Yue (Chemical Engineering Journal, 2023)

Evolutional solid phase and solid-liquid interface uranium immobilization mechanisms by nanoscale zero-valent iron and enhanced uranium stability control strategy - Yilong Hua; Donghan Li; Jinglan Zou; Wei Wang; Xiaoyan Wu; Xiaowen Zhang; Qing Liu; Guodong Zhao; Mi Li; Wei-xian Zhang; Jianping Yang (Chemical Engineering Journal, 2023)

Intermetallic niobium boride toward efficient adsorption and catalysis of polysulfides in Lithium-Sulfur batteries - Li He; Yingjie Cheng; Qiuju Li; Hainan Zhao; Meiling Wang; Xuejian Shi; Xiaoxin Zou; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

The association between exposure to multiple toxic metals and the risk of endometriosis: Evidence from the results of blood and follicular fluid - Lingchao Shen; Chunmei Liang; Danyang Li; Zhikang Zhang; Xin Wang; Tingting Jiang; Xun Su; Tao Yin; Weiwei Zou; Xiaolei Wang; Yajing Liu; Dan Liang; et al. (Science of The Total Environment, 2023)

Efficient removal of bisphenol A by a novel biochar-based Fe/C granule via persulfate activation: Performance, mechanism, and toxicity assessment - Xiang Li; Yang Qin; Huajing Song; Wei Zou; Zhiguo Cao; Linjie Ding; Yuwei Pan; Minghua Zhou (Process Safety and Environmental Protection, 2023)

Petrogenesis of late Cenozoic high Mg andesites with high Nb/Ta ratios in Northern Songliao Basin, NE China - Yong-wei Zhao; Haibo Zou; Ni Li (Lithos, 2023)

Functional polypropylene fibers sphere combined with citric acid for efficient remediation of heavily cadmium (Cd) contaminated soil based on adsorption and citric acid recycling - Kaijian Zou; Junfu Wei; Li Cui; Zhiyun Kong; Huan Zhang; Changchang Niu; Xiaolei Wang; Huicai Wang (Journal of Cleaner Production, 2023)

Polyethylene microplastics can attenuate soil carbon sequestration by reducing plant photosynthetic carbon assimilation and transfer: evidence from a 13C-labeling mesocosm study - Ziqiang Liu; Zhijun Su; Jiayi Chen; Jiayu Zou; Zhenxiu Liu; Yazheng Li; Jing Wang; Lizhu Wu; Hui Wei; Jiaen Zhang (Journal of Cleaner Production, 2023)

Modulating interfacial charge distribution of NiSe nanoarrays with NiFe-LDH nanosheets for boosting oxygen evolution reaction - Weiwei Bao; Chunming Yang; Taotao Ai; Junjun Zhang; Lihai Zhou; Yan li; Xueling Wei; Xiangyu Zou; Yong Wang (Fuel, 2023)

Experimental study on thermochemical composite system huff-n-puff process in ultra-heavy oil production - Na Zhang; Wei Liu; Xuefei Zou; Shaochun Wang; Qian Sun; Binfei Li; Songyan Li; Aabiskar Bhusal; Shuhua Wang; Zhaomin Li (Fuel, 2023)

Relationship of multiple metals mixture and osteoporosis in older Chinese women: An aging and longevity study - Xiuming Feng; Gaohui Zan; Yue Wei; Xiaoting Ge; Haiqing Cai; Tianzhu Long; Lianguang Xie; Lei Tong; Chaoqun Liu; Longman Li; Lulu Huang; Fei Wang; et al. (Environmental Pollution, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Self-healing properties of retrograded starch films with enzyme-treated waxy maize starch as healing agent - Li Guo; Na Yang; Wei Gao; Haiteng Tao; Bo Cui; Pengfei Liu; Feixue Zou; Lu Lu; Yishan Fang; Zhengzong Wu (Carbohydrate Polymers, 2023)

Comprehensive genetic analysis reveals seed germination activity-related QTL and meta-QTL in rice (Oryza sativa L.) - Pen Li; Hualong Liu; Haoran Wen; Luomiao Yang; Ziqi Chen; Hongliang Zheng; Wei Xin; Dezhuang Zhang; Jingguo Wang; Detang Zou (Genetic Resources and Crop Evolution, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

FUS Mutation Causes Disordered Lipid Metabolism in Skeletal Muscle Associated with ALS - Binbin Zhou; Yilei Zheng; Xiaobing Li; Huifang Dong; Jiaxi Yu; Yang Zou; Min Zhu; Yanyan Yu; Xin Fang; Meihong Zhou; Wei Zhang; Yun Yuan; et al. (Molecular Neurobiology, 2022)

Geomorphic and tectonic controls of landslides induced by the 2022 Luding earthquake - Bo Zhao; Kai-heng Hu; Zong-ji Yang; Qiao Liu; Qiang Zou; Hua-yong Chen; Bo Zhang; Wei-feng Zhang; Lei Zhu; Li-jun Su (Journal of Mountain Science, 2022)

Effects of Different Oxytocin and Temperature on Reproductive Activity in Nile tilapia (Oreochromis niloticus): Based on Sex Steroid Hormone and GtHR Gene Expression - Jie Yu; Dayu Li; Jinglin Zhu; Zhiying Zou; Wei Xiao; Binglin Chen; Hong Yang (Fishes, 2022)
Luteinizing hormone receptor (LHR) and follicle-stimulating hormone receptor (FSHR) belong to the gonadotropic hormone receptors (GtHR), which are highly expressed in fish gonads and participate in the regulation of fish reproductive activities. Fish gonadal development and gamete maturation are not only regulated by their BPG axis but also affected by natural environmental factors (such as temperature, salinity, pH, nutrients, light, etc.). Nile tilapia (Oreochromis niloticus) is a farmed fish with a short reproductive cycle, fast growth, and high economic value. To study the relationship between gonadotropic hormone receptors (GtHR) and the reproductive activity of Nile tilapia, different oxytocin injection experiments and different temperature treatment experiments were set up, and the expression changes of the GtHR gene in the gonads and the concentration changes of the estradiol (E2) in the female serum and testosterone (T) in the male serum were determined employing a quantitative RT-PCR assay and enzyme-linked immunosorbent assay (ELISA), respectively. After the injection of oxytocin, with the change of E2 in females and T in males, the FSHR showed an expression pattern of first increase, then decrease, and the LHR showed an expression pattern of first increase, then decrease, and finally increase in the gonads, and the expression level of FSHR and LHR in the injection group was significantly higher than that in the control group at multiple time points; in addition, the expression level of FSHR and LHR in the oxytocin-combination injection group was higher than that in the single injection group. During 28 days of treatment at different temperatures, the sex steroid hormones and GtHR genes also showed regular changes, and the relationship between each group was 28 °C > 32 °C > 24 °C at most time points. According to the research results, it is speculated that FSHR and LHR play an important role in the development of Nile tilapia gonads and participate in the reproductive activities of Nile tilapia. By comparing and analyzing the changes in the sex steroid hormones and GtHR genes in each experimental group, it is speculated that different oxytocin injections could affect the expression of FSHR and LHR genes in Nile tilapia, and the combined effect of oxytocin was better than single oxytocin; the optimum temperature for the reproduction of Nile tilapia is between 28–32 °C. This study provides a theoretical basis for further elucidating the physiological functions and molecular mechanisms of FSHR and LHR and also provides a reference for the research of reproductive regulation in Nile tilapia.

Oxidative stress responses in the respiratory tree and the body wall of sea cucumber Apostichopus japonicus (Selenka) to high temperature - Zhonglei Ju; Guoxiang Liao; Yulu Zhang; Nan Li; Xishan Li; Yuhang Zou; Wei Yang; Deqi Xiong (Environmental Science and Pollution Research, 2022)

Impact of Physically and Chemically Dispersed Crude Oil on the Antioxidant Defense Capacities and Non-Specific Immune Responses in Sea Cucumber (Apostichopus japonicus) - Xishan Li; Yuhang Zou; Hao Xuan; Wei Yang; Guoxiang Liao; Chengyan Wang; Deqi Xiong (Journal of Marine Science and Engineering, 2022)
Currently, oil spill pollution is one of the major environmental concerns for sea cucumber (Apostichopus japonicus) aquaculture. During oil spills, spraying chemical dispersants is generally considered an efficient oil spill response. However, the impact of chemical dispersant deployment during oil spills on sea cucumbers is still less known. In this study, we treated sea cucumbers with physically and chemically (by GM-2 chemical dispersant) dispersed Oman crude oil for 24 h. For antioxidant defense capacities, our results showed that physically dispersed crude oil caused a significant elevation on superoxide dismutase (SOD) and catalase (CAT) activities, and glutathione (GSH) content, while chemically dispersed crude oil caused a significant decrease in SOD activity and GSH content with no apparent change in CAT activity. As for non-specific immune responses, our results indicated that physically dispersed crude oil up-regulated acid phosphatase (ACP) and lysozyme (LZM) activities but had no obvious impact on alkaline phosphatase (ALP) activity. Differently, chemically dispersed crude oil down-regulated ACP and LZM activities while up-regulating ALP activity. Based on the integrated biomarker response analysis, the overall impact of chemically dispersed crude oil on antioxidant defense capacities and non-specific immune responses of sea cucumbers was more severe than physically dispersed crude oil.

Modeling of CSTR flow field for Agaricus bisporus residue fermentation based on CFD numerical simulation - Jiayu Li; Jinping Zou; Xuan Wei (Environmental Science and Pollution Research, 2022)

Identification of a 5-gene-risk score model for predicting luminal A-invasive lobular breast cancer survival - Yi-Huan Chen; Tao-Feng Zhang; Yi-Yuan Liu; Jie-Hua Zheng; Wei-Xun Lin; Yao-Kun Chen; Jie-Hui Cai; Juan Zou; Zhi-Yang Li (Genetica, 2022)

Characteristics, Types, and Prospects of Geological Sweet Sections in Giant Continental Shale Oil Provinces in China - Zhi Yang; Caineng Zou; Songtao Wu; Songqi Pan; Xiaoni Wang; Haitao Liu; Wenqi Jiang; Jiarui Li; Qiyan Li; Xiaobing Niu; Guohui Li; Zhenxing Tang; et al. (Journal of Earth Science, 2022)

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Astrocyte Activation, but not Microglia, Is Associated with the Experimental Mouse Model of Schizophrenia Induced by Chronic Ketamine - Ying Wei; Li Xiao; Weihao Fan; Jing Zou; Hong Yang; Bo Liu; Yi Ye; Di Wen; Linchuan Liao (Journal of Molecular Neuroscience, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Andrographolide Attenuates Blood–Brain Barrier Disruption, Neuronal Apoptosis, and Oxidative Stress Through Activation of Nrf2/HO-1 Signaling Pathway in Subarachnoid Hemorrhage - Pian Gong; Wei Zhang; Changlin Zou; Shoumeng Han; Qi Tian; Jianfeng Wang; Peibang He; Yujia Guo; Mingchang Li (Neurotoxicity Research, 2022)

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Working Performance of the Deep-Sea Valve-Controlled Hydraulic Cylinder System under Pressure-Dependent Viscosity Change and Hydrodynamic Effects - Jia-Bin Wu; Li Li; Xing-Long Zou; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly used for actuators such as manipulators in deep-sea equipment, whose working performance is crucial to subsea tasks. Affected by the ambient pressure introduced by the pressure compensator, the viscosity of the hydraulic oil increases significantly. On this basis, the viscosity changes further when flowing in the slender pipeline, making the pipeline pressure loss substantially increase and subsequently affecting the working performance of the deep-sea VCHCS. Aiming at this issue, a detailed nonlinear mathematical model of the deep-sea VCHCS is established, in which the viscosity-pressure characteristics of the hydraulic oil is considered to take the viscosity changes in the pipeline into account. Besides, the hydrodynamic effects are also included in the model. Then the corresponding numerical simulation model of the deep-sea VCHCS is established, and its working performance at different depths is simulated and analyzed. When the depth is 11km, the extension and retraction movements are delayed by 52.50% and 43.12% respectively. The root cause of the delay is then analyzed and discussed. Finally, the parameters that affect the working performance are studied, and suggestions to reduce or eliminate the delay phenomenon are given. The results can provide theoretical support for the performance optimization of the deep-sea VCHCS.

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Transcriptome Profiling Revealed Basis for Growth Heterosis in Hybrid Tilapia (Oreochromis niloticus ♀ × O. aureus ♂) - Jinglin Zhu; Zhiying Zou; Dayu Li; Wei Xiao; Jie Yu; Binglin Chen; Liangyi Xue; Hong Yang (Fishes, 2022)
Hybrid tilapia were produced from hybridization of Nile tilapia (Oreochromis niloticus) and blue tilapia (O. aureus). Comparative transcriptome analysis was carried out on the liver of hybrid tilapia and their parents by RNA sequencing. A total of 2319 differentially expressed genes (DEGs) were identified. Trend co-expression analysis showed that non-additive gene expression accounted for 67.1% of all DEGs. Gene Ontology and KEGG enrichment analyses classified the respective DEGs. Gene functional enrichment analysis indicated that most up-regulated genes, such as FASN, ACSL1, ACSL3, ACSL6, ACACA, ELOVL6, G6PD, ENO1, GATM, and ME3, were involved in metabolism, including fatty acid biosynthesis, unsaturated fatty acid biosynthesis, glycolysis, pentose phosphate pathway, amino acid metabolism, pyruvate metabolism, and the tricarboxylic acid cycle. The expression levels of a gene related to ribosomal biosynthesis in eukaryotes, GSH-Px, and those associated with heat shock proteins (HSPs), such as HSPA5 and HSP70, were significantly down-regulated compared with the parent tilapia lineages. The results revealed that the metabolic pathway in hybrid tilapia was up-regulated, with significantly improved fatty acid metabolism and carbon metabolism, whereas ribosome biosynthesis in eukaryotes and basal defense response were significantly down-regulated. These findings provide new insights into our understanding of growth heterosis in hybrid tilapia.

Analysis of volatile organic compounds in exhaled breath after radiotherapy - Dianlong Ge; Xue Zou; Yajing Chu; Jijuan Zhou; Wei Xu; Yue Liu; Qiangling Zhang; Yan Lu; Lei Xia; Aiyue Li; Chaoqun Huang; Pei Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Effect of Temperature on the Acoustic Reflection Characteristics of Seafloor Surface Sediments - Dapeng Zou; Guican Ye; Wei Liu; Han Sun; Jun Li; Tibing Xiao (Journal of Ocean University of China, 2022)

The miR-214-3p/c-Ski axis modulates endothelial–mesenchymal transition in human coronary artery endothelial cells in vitro and in mice model in vivo - Juan Wang; Hongjian Li; Zhongying Lv; Xiaomei Luo; Wei Deng; Ting Zou; Yue Zhang; Wanyue Sang; Xuehua Wang (Human Cell, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

The Mojiawan I-type granite of the Kangding Complex in the western Yangtze Block: new constraint on the Neoproterozoic magmatism and tectonic evolution of South China - Xiu-Wei Jiang; Hao Zou; Leon Bagas; Hai-Feng Chen; Hang Liu; Yang Li; Min Li; Die Li (International Geology Review, 2021)

Identification and Expression Analyses of the Special 14–3-3 Gene Family in Papaya and its Involvement in Fruit Development, Ripening, and Abiotic Stress Responses - Meiying Li; Licheng Ren; Zhi Zou; Wei Hu; Susheng Xiao; Xiaoliang Yang; Zehong Ding; Yan Yan; Weiwei Tie; Jinghao Yang; Anping Guo (Biochemical Genetics, 2021)

Nanoplastics Induce More Serious Microbiota Dysbiosis and Inflammation in the Gut of Adult Zebrafish than Microplastics - Shaolin Xie; Aiguo Zhou; Tianli Wei; Siying Li; Bing Yang; Guohuan Xu; Jixing Zou (Bulletin of Environmental Contamination and Toxicology, 2021)

Acupuncture Ameliorates Neuronal Cell Death, Inflammation, and Ferroptosis and Downregulated miR-23a-3p After Intracerebral Hemorrhage in Rats - Ying Kong; Shulin Li; Miao Zhang; Wenting Xu; Qiuxin Chen; Lihong Zheng; Peng Liu; Wei Zou (Journal of Molecular Neuroscience, 2021)

Identification of glutathione transferase gene associated with partial resistance to Sclerotinia stem rot of soybean using genome-wide association and linkage mapping - Zou Jianan; Wenjing Li; Yuting Zhang; Wei Song; Haipeng Jiang; Jingyun Zhao; Yuhang Zhan; Weili Teng; Lijuan Qiu; Xue Zhao; Yingpeng Han (Theoretical and Applied Genetics, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

SR-B1 and CD10 combined immunoprofile for differential diagnosis of metastatic clear cell renal cell carcinoma and clear cell carcinoma of the ovary - Teng Jiang; Xiaoli Diao; Meili Ding; Xiao Niu; Chao Wang; Yan Qi; Wei Jia; Lijuan Pang; Wenhao Hu; Hong Zou; Feng Li (Journal of Molecular Histology, 2021)
Both clear cell renal carcinoma (ccRCC) and clear cell carcinoma of the ovary (CCOC) have a clear cytoplasmic morphological feature, hence it is difficult to identify metastatic ccRCC and CCOC by morphology alone. At present, there are no effective immunohistochemical markers to distinguish between these two tumors. Studies have shown that the clear cytoplasm of ccRCC is mainly caused by cholesterol-rich lipids in the cytoplasm, while that of CCOC is due to the accumulation of cytoplasmic glycogen. Objective: to hypothesize that the scavenger receptor class B-type 1 (SR-B1) protein responsible for HDL cholesterol uptake may be differentially expressed in ccRCC and CCOC, and high CD10 expression in the renal tubular epithelium may assist in distinguishing between ccRCC and CCOC. Methods: effective immunohistochemical markers were applied in 90 cases of renal clear cell carcinoma and 31 cases of ovarian cancer to distinguish between the two types of tumors.Result: SR-B1 and CD10 expression is significantly higher in ccRCC than CCOC. Both SR-B1 and CD10 exhibited focal weak-medium intensity staining in CCOC, and their staining extent and intensity were significantly lower than ccRCC. The sensitivity and specificity of SR-B1 for identifying ccRCC were 74.4% and 83.9%, respectively. The sensitivity and specificity of CD10 for identifying CCOC were 93.3% and 80.6%, respectively. The combined SR-B1( +) CD10( +) immunoprofile supports the diagnosis of ccRCC with a specificity of 93.5%. The combined SR-B1(-) CD10(-) immunoprofile supports the diagnosis of CCOC with a specificity of 93.3%. Conclusions: our findings demonstrate that the combination of SR-B1 and CD10 immunoprofiling is a valuable tool for differential diagnosis of ccRCC and CCOC.

Risk assessment of glacial debris flow on alpine highway under climate change: A case study of Aierkuran Gully along Karakoram Highway - Ya-mei Li; Li-jun Su; Qiang Zou; Xue-li Wei (Journal of Mountain Science, 2021)

Combining forecast of landslide displacement based on chaos theory - Xunchang Li; Chao Jiang; Rui Xu; Wei Yang; HaoHao Wang; Yu Zou (Arabian Journal of Geosciences, 2021)

Determination of fracture energy and fracture toughness of two types of concrete and their interface - Wei Chen; Wangyang Xie; Xiang Li; Wenjie Zou; Helin Fu (European Journal of Environmental and Civil Engineering, 2021)

Progress and prospects of applied research on physical geography and the living environment in China over the past 70 years (1949–2019) - Fahu Chen; Shaohong Wu; Peng Cui; Yunlong Cai; Yili Zhang; Yunhe Yin; Guobin Liu; Zhu Ouyang; Wei Ma; Linsheng Yang; Duo Wu; Jiaqiang Lei; et al. (Journal of Geographical Sciences, 2021)

Identification of Amino Acid Dysregulation as a Potential Biomarker for Autism Spectrum Disorder in China - Mingyang Zou; Dexin Li; Luxi Wang; Ling Li; Shu Xie; Yu Liu; Wei Xia; Caihong Sun; Lijie Wu (Neurotoxicity Research, 2020)

Antibacterial effect of Blumea balsamifera DC. essential oil against Haemophilus parasuis - Changliang He; Peiyi Yang; Lu Wang; Xiaolin Jiang; Wei Zhang; Xiaoxia Liang; Lizi Yin; Zhongqiong Yin; Yi Geng; Zhijun Zhong; Xu Song; Yuanfeng Zou; et al. (Archives of Microbiology, 2020)

Patterns of presence-absence variants in Upland cotton - Junfang Liu; Xianliang Zhang; Lingling Dou; Wei Li; Xiaojian Zhou; Yangai Liu; Xiaoyu Pei; Zhongying Ren; Wensheng Zhang; Huaizhu Li; Wenbo Wang; Changsong Zou; et al. (Science China Life Sciences, 2020)

Correction to: LncRNA NONRATT021972 involved the pathophysiologic processes mediated by P2X7 receptors in stellate ganglia after myocardial ischemic injury - Lifang Zou; Guihua Tu; Wei Xie; Shiyao Wen; Qiuyu Xie; Shuangmei Liu; Guilin Li; Yun Gao; Hong Xu; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2020)

An APETALA2/ethylene responsive factor, OsEBP89 knockout enhances adaptation to direct-seeding on wet land and tolerance to drought stress in rice - Yu Zhang; Jia Li; Shoujun Chen; Xiaosong Ma; Haibin Wei; Chen Chen; Ningning Gao; Yuqiao Zou; Deyan Kong; Tianfei Li; Zaochang Liu; Shunwu Yu; et al. (Molecular Genetics and Genomics, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

The acute effects of ultraviolet radiation exposure on solar dermatitis in Shanghai, China - Guojiang Zhou; Li Peng; Wei Gao; Ying Zou; Yimei Tan; Yangfeng Ding; Shanqun Li; Hong Sun; Renjie Chen (International Journal of Biometeorology, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Evaluation of phage therapy in the treatment of Staphylococcus aureus-induced mastitis in mice - Huijun Geng; Wei Zou; Meixia Zhang; Le Xu; Fanming Liu; Xiaoyu Li; Lili Wang; Yongping Xu (Folia Microbiologica, 2020)

Bamboo nutrients and microbiome affect gut microbiome of giant panda - Lei Jin; Daifu Wu; Caiwu Li; Anyun Zhang; Yaowu Xiong; Rongping Wei; Guiquan Zhang; Shengzhi Yang; Wenwen Deng; Ti Li; Bei Li; Xin Pan; et al. (Symbiosis, 2020)

Cascading effects of elevation, soil moisture and soil nutrients on plant traits and ecosystem multi-functioning in Poyang Lake wetland, China - Hui Fu; Guixiang Yuan; Dabing Ge; Wei Li; Dongsheng Zou; Zhenrong Huang; Aiping Wu; Qiaolin Liu; Erik Jeppesen (Aquatic Sciences, 2020)

Isolation, structure elucidation, tyrosinase inhibitory, and antioxidant evaluation of the constituents from Angelica dahurica roots - Penghua Shu; Junping Li; Yingying Fei; Huiqing Zhu; Mengzhu Yu; Anqi Liu; Haoying Niu; Simin Zou; Xialan Wei; Zhiyu Ju; Zhihong Xu (Journal of Natural Medicines, 2020)

Plastidial and ER Triacylglycerol Biosynthesis in a Growth Phase-Dependent Manner in the Heterokont Nannochloropsis oceanica - Dan Huang; Da-Wei Li; Srinivasan Balamurugan; Jian-Wei Zheng; Wan-Jun Liu; Li-Gong Zou; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Frontiers in Marine Science, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

Asperpyrone F, a new dimeric naphtho- γ -pyrone from the edible fungus Pleurotus ostreatus - Xu Cai; Yang Yu; Qian Li; Ben-Ke Chen; Yun Huang; Xian-Wei Zou; Jin-Tian Tang; Bi-Sheng Huang (Natural Product Research, 2019)

Adoptive transfer of IFN-γ-induced M-MDSCs promotes immune tolerance to allografts through iNOS pathway - Fan Yang; Yang Li; Weilong Zou; Yanan Xu; Hao Wang; Wei Wang; Yong Zhao (Inflammation Research, 2019)

Upregulation of phosphoinositide 3-kinase prevents sunitinib-induced cardiotoxicity in vitro and in vivo - Congxin Li; Ruya Zou; Hua Zhang; Yuhong Wang; Bo Qiu; Suhua Qiu; Wei Wang; Yanfang Xu (Archives of Toxicology, 2019)

Protein interactions of SOC1 with SVP are regulated by a few crucial amino acids in flowering pathways of Brassica juncea - Chaochuang Li; Huiying Gu; Wei Jiang; Chenhui Zou; Dayong Wei; Zhimin Wang; Qinglin Tang (Acta Physiologiae Plantarum, 2019)

Antibacterial activity and mechanism of ThDP analogs against rice brown stripe pathogen Acidovorax avenae subsp. avenae RS-1 - Xiao Xuan Wang; Hang Ying Qi; Jie Chen; Ying Zi Yang; Wen Qiu; Wei Wang; Peng Zou; Bin Li; Yan Li Wang; Hong Wu He; Guo Chang Sun (Journal of Plant Pathology, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Pharmacokinetics of enrofloxacin and its metabolite ciprofloxacin in Pacific white shrimp Litopenaeus vannamei after multiple-dose oral administration - Rongrong Ma; Liang Huang; Wenjuan Wei; Yuan Wang; Xiong Zou; Junfang Zhou; Xincang Li; Wenhong Fang (Fisheries Science, 2018)

The Antibacterial Mechanism of Terpinen-4-ol Against Streptococcus agalactiae - Yuetian Zhang; Ruizhang Feng; Lixia Li; Xun Zhou; Zhengwen Li; Renyong Jia; Xu Song; Yuanfeng Zou; Lizi Yin; Changliang He; Xiaoxia Liang; Wanhai Zhou; et al. (Current Microbiology, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Complete genome sequence of the sesame pathogen Ralstonia solanacearum strain SEPPX 05 - Xinshen Li; Xiaomei Huang; Gongyou Chen; Lifang Zou; Lingen Wei; Juling Hua (Genes & Genomics, 2018)

Chinese Marine Economy Development: Dynamic Evolution and Spatial Difference - Caizhi Sun; Xin Li; Wei Zou; Song Wang; Zeyu Wang (Chinese Geographical Science, 2018)

A new bisabolane sesquiterpenoid and a new abietane diterpenoid from Cephalotaxus sinensis - Abrar Ahmed; Wei Li; Jun-Sheng Zhang; Pek-Ha Sam; Yi-Hong Zou; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

The D‐lactate dehydrogenase MoDLD1 is essential for growth and infection‐related development in Magnaporthe oryzae - Tengsheng Zhou; Li Qin; Xiaohan Zhu; Wenyun Shen; Jitao Zou; Zonghua Wang; Yangdou Wei (Environmental Microbiology, 2017)
Summary Rice blast disease caused by Magnaporthe oryzae is initiated by the attachment of conidia to plant surfaces. Germ tubes emerging from conidia develop melanized appressoria to physically penetrate the host surface. Previous studies revealed that appressorium development requires the breakdown of storage lipids and glycogen that occur in peroxisomes and the cytosol respectively, culminating in production of pyruvate. However, the downstream product(s) entering the mitochondria for further oxidation is unclear. In this study, we aimed to investigate the molecular basis underlying the metabolic flux towards the mitochondria associated with the infectious‐related development in M. oryzae . We showed that D‐lactate is a key intermediate metabolite of the mobilization of lipids and glycogen, and its oxidative conversion to pyruvate is catalysed by a mitochondrial D‐lactate dehydrogenase MoDLD1. Deletion of MoDLD1 caused defects in conidiogenesis and appressorium formation, and subsequently the loss of fungal pathogenicity. Further analyses demonstrated that MoDLD1 activity is involved in the maintenance of redox homeostasis during conidial germination. Thus, MoDLD1 is a critical modulator that channels metabolite flow to the mitochondrion coupling cellular redox state, and contributes to development and virulence of M. oryzae .

Cerebral functional deficits in patients with ankylosing spondylitis- an fMRI study - Chuanming Li; Xin Wei; Qinghua Zou; Yi Zhang; Xuntao Yin; Jun Zhao; Jian Wang (Brain Imaging and Behavior, 2017)

COP9 signalosome subunit PfCsnE regulates secondary metabolism and conidial formation in Pestalotiopsis fici - Yanjing Zheng; Xiuna Wang; Xiaoling Zhang; Wei Li; Gang Liu; Shihua Wang; Xiufeng Yan; Huixi Zou; Wen-Bing Yin (Science China Life Sciences, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Activation of the TXNIP/NLRP3 inflammasome pathway contributes to inflammation in diabetic retinopathy: a novel inhibitory effect of minocycline - Wei Chen; Minjie Zhao; Shuzhi Zhao; Qianyi Lu; Lisha Ni; Chen Zou; Li Lu; Xun Xu; Huaijin Guan; Zhi Zheng; Qinghua Qiu (Inflammation Research, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Household environment, lifestyle behaviors, and dietary habits in relation to childhood atopic eczema in Shanghai, China - Jiao Cai; Wei Liu; Yu Hu; Zhijun Zou; Li Shen; Chen Huang (International Archives of Occupational and Environmental Health, 2017)

Screening of Bacillus Strains from Sun Vinegar for Efficient Production of Flavonoid and Phenol - Changqing Zhao; Xingxiu Zhao; Jing Zhang; Wei Zou; Yi Zhang; Li Li; Jun Liu (Indian Journal of Microbiology, 2016)

Discovery and characterization of a first set of polymorphic microsatellite markers in red crab (Charybdis feriatus) - HONGYU MA; XIONG ZOU; XIANGSHAN JI; CHUNYAN MA; JIANXUE LU; WEI JIANG; LIANJUN XIA; SHUJUAN LI; YUEXING LIU; YANGYANG GONG; LINGBO MA (Journal of Genetics, 2016)

Augmented expression of gamma-glutamyl transferase 5 (GGT5) impairs testicular steroidogenesis by deregulating local oxidative stress - Wei Li; Zhi-qun Wu; Shun Zhang; Rui Cao; Jie Zhao; Zhi-jian Sun; Wei Zou (Cell and Tissue Research, 2016)

The effects of NONRATT021972 lncRNA siRNA on PC12 neuronal injury mediated by P2X7 receptor after exposure to oxygen-glucose deprivation - Guilin Li; Lifang Zou; Wei Xie; Shiyao Wen; Qiuyu Xie; Yun Gao; Changshui Xu; Hong Xu; Shuangmei Liu; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2016)

Expression of KCNA5 Protein in Human Mammary Epithelial Cell Line Associated with Caveolin-1 - Jia Liu; Chao Qu; Hongyan Li; Yejun Zhang; Jia Sun; Shuo Yang; Jing Liu; Lijia An; Wei Zou (The Journal of Membrane Biology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Solar-, monsoon- and Kuroshio-influenced thermocline depth and sea surface salinity in the southern Okinawa Trough during the past 17,300 years - Libo Wang; Jun Li; Jingtao Zhao; Helong Wei; Bangqi Hu; Yanguang Dou; Zhilei Sun; Liang Zou; Fenglong Bai (Geo-Marine Letters, 2016)

DNA barcoding of recently diversified tree species: a case study on spruces based on 20 DNA fragments from three different genomes - Jiabin Zou; Wei Yue; Lili Li; Xi Wang; Jing Lu; Bingbing Duan; Jianquan Liu (Trees, 2016)

MRP functional activity and character in the dinoflagellate Prorocentrum lima - Dao-yi Hou; Jin-jin Liang; Cheng Zou; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

LncRNA NONRATT021972 involved the pathophysiologic processes mediated by P2X7 receptors in stellate ganglia after myocardial ischemic injury - Lifang Zou; Guihua Tu; Wei Xie; Shiyao Wen; Qiuyu Xie; Shuangmei Liu; Guilin Li; Yun Gao; Hong Xu; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Long-term effects of oral tea polyphenols and Lactobacillus brevis M8 on biochemical parameters, digestive enzymes, and cytokines expression in broilers - Hua-li Li; Zong-jun Li; Zhong-shan Wei; Ting Liu; Xiao-zuo Zou; Yong Liao; Yu Luo (Journal of Zhejiang University-SCIENCE B, 2015)

Protective Effect of Porcine Cerebral Hydrolysate Peptides on Learning and Memory Deficits and Oxidative Stress in Lead-Exposed Mice - Ye Zou; Weiwei Feng; Wei Wang; Yao Chen; Zhaoxiang Zhou; Qian Li; Ting Zhao; Guanghua Mao; Xiangyang Wu; Liuqing Yang (Biological Trace Element Research, 2015)

Preseismic deformation in the seismogenic zone of the Lushan M S7.0 earthquake detected by GPS observations - XiaoXia Liu; YanQiang Wu; ZaiSen Jiang; Wei Zhan; Qiang Li; WenXin Wei; ZhenYu Zou (Science China Earth Sciences, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Origin and speciation of Picea schrenkiana and Picea smithiana in the Center Asian Highlands and Himalayas - Lili Li; Yongshuai Sun; Jiabin Zou; Wei Yue; Xi Wang; Jianquan Liu (Plant Molecular Biology Reporter, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Dietary threonine requirement of juvenile Nile tilapia, Oreochromis niloticus - Yirong Yue; Zhiying Zou; Jinglin Zhu; Dayu Li; Wei Xiao; Jue Han; Hong Yang (Aquaculture International, 2014)

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Shuang Liang; Xue-lai Wang; Ming-yang Zou; Han Wang; Xue Zhou; Cai-hong Sun; Wei Xia; Li-jie Wu; Takashi X. Fujisawa; Akemi Tomoda (Journal of Zhejiang University-SCIENCE B, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Zinc fertilizer placement affects zinc content in maize plant - Yue-Qiang Zhang; Li-Li Pang; Peng Yan; Dun-Yi Liu; Wei Zhang; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

The Expression Patterns of Septin-9 After Traumatic Brain Injury in Rat Brain - Hui Mao; Jiao Liu; Wei Shi; Qingfeng Huang; Xide Xu; Lanchun Ni; Feihui Zou; Jinlong Shi; Debao Li; Yonghua Liu; Jian Chen (Journal of Molecular Neuroscience, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Isolation and characterization of eleven novel microsatellite loci of Brachymystax lenok tsinlingensis, a threatened fish endemic to Shaanxi, China - Haixia Liu; Yang Li; Xiaolin Liu; Guiwei Zou; Qiwei Wei (Conservation Genetics Resources, 2013)

Destrin deletion enhances the bone loss in hindlimb suspended mice - Feng Shuang; Yu Sun; Huai-He Yang; Yin-Chu Shao; Hao Li; Wei Hu; Jun Zhong; Hong-Xing Zou (European Journal of Applied Physiology, 2013)

Cervical cancer with polymorphism in MTHFR C677T gene: a systematic review and meta-analysis - Xiao-juan Xu; Li-wei Zou; De-bin Wang (Molecular Biology Reports, 2013)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Meta-analysis of MCP-1 promoter −2518 A/G polymorphism and SLE susceptibility - Ting Liu; Jin-Xia Zhai; Han-Yong Wang; Xing-Hua Wang; Li-Wei Zou; Wen-jing Fan; Dong-Qing Ye (Molecular Biology Reports, 2012)

PDTC attenuate LPS-induced kidney injury in systemic lupus erythematosus-prone MRL/lpr Mice - Jin-Xia Zhai; Zhao-Xiang Zhang; Ya-Juan Feng; Shu-Shu Ding; Xing-Hua Wang; Li-Wei Zou; Dong-Qing Ye (Molecular Biology Reports, 2012)

Forewarning of sustainable utilization of regional water resources: a model based on BP neural network and set pair analysis - Ju-Liang Jin; Yi-Ming Wei; Le-Le Zou; Li Liu; Wei-wei Zhang; Yu-liang Zhou (Natural Hazards, 2012)

Risk evaluation of China’s natural disaster systems: an approach based on triangular fuzzy numbers and stochastic simulation - Ju-Liang Jin; Yi-Ming Wei; Le-Le Zou; Li Liu; Juan Fu (Natural Hazards, 2012)

Update analysis of studies on the MMP-9 −1562 C>T polymorphism and cancer risk - Li-Feng Zhang; Yuan-Yuan Mi; Qiang Cao; Wei Wang; Chao Qin; Jun-Feng Wei; Yao-Jun Zhou; Yong-Fei Li; Min Tang; Wei-Min Liu; Wei Zhang; Jian-Gang Zou (Molecular Biology Reports, 2012)

Characteristics, timing, and offsets of the middle-southern segment of the western boundary strike-slip fault of the Songliao Basin in Northeast China - GuoQing Han; YongJiang Liu; Franz Neubauer; Johann Genser; YunXin Zou; Wei Li; ChenYue Liang (Science China Earth Sciences, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Development and application of a set of breeder-friendly SNP markers for genetic analyses and molecular breeding of rice (Oryza sativa L.) - Haodong Chen; Hang He; Yanjiao Zou; Wei Chen; Renbo Yu; Xia Liu; Yang Yang; Yong-Ming Gao; Jian-Long Xu; Liu-Min Fan; Yi Li; Zhi-Kang Li; et al. (Theoretical and Applied Genetics, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Settlement of vegetative fragments of Ulva prolifera confirmed as an important seed source for succession of a large‐scale green tide bloom - Xiaowen Zhang; Dong Xu; Yuze Mao; Youxun Li; Suyan Xue; Jian Zou; Wei Lian; Chengwei Liang; Zhimeng Zhuang; Qingyin Wang; Naihao Ye (Limnology and Oceanography, 2011)
Ulva prolifera green tides in the Yellow Sea of China in the past 3 yr are among the largest macroalgal blooms ever recorded. Satellite images, as well as wind and current patterns, provide a clear picture of the formation of these green tides; however, their place of origin remains unclear. Terrestrial investigation along the coastline of the Jiangsu Province and two shipboard surveys in the Yellow Sea in 2009 showed that filamentous Ulvaceae algae were prevalent in various environments in Jiangsu Province including floating rafts for Porphyra cultivation, land‐based bivalve culturing ponds, estuaries, embankments, intertidal stones, wharfs, and hard muddy coasts. Vegetative fragments in sediment samples were found in both shipboard surveys during the bloom and postbloom periods, and all of the samples were U. prolifera . Phylogenetic analysis of 5S spacer sequences showed that the green tide in the Yellow Sea was not of terrestrial origin. However, settled vegetative fragments of U. prolifera were an important seed source for the successive and more serious green tide blooms.

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

The global image of the Moon obtained by the Chang’E-1: Data processing and lunar cartography - ChunLai Li; JianJun Liu; Xin Ren; LingLi Mou; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; et al. (Science China Earth Sciences, 2010)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Isolation and characterization of polymorphic microsatellite markers in the yellow catfish, Pelteobagrus fulvidraco - Guang-Fu Hu; Hong-Wei Liang; Zhong Li; Chang-Zhong Wang; Qin-Chao Wu; Xiang-Jiang Liu; Xiang-Zhong Luo; Gui-Wei Zou (Conservation Genetics Resources, 2009)

Screening and identification of natural antisense transcripts in Helicobacter pylori by a novel approach based on RNase I protection assay - Bin Xiao; Wei Li; Gang Guo; Bo-Sheng Li; Zhen Liu; Bin Tang; Xu-Hu Mao; Quan-Ming Zou (Molecular Biology Reports, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Isolation and molecular characterization of equine H3N8 influenza viruses from pigs in China - Jiagang Tu; Hongbo Zhou; Taozhen Jiang; Chun Li; Anding Zhang; Xuebo Guo; Wei Zou; Huanchun Chen; Meilin Jin (Archives of Virology, 2009)

Identification of Small Noncoding RNAs in Helicobacter pylori by a Bioinformatics-Based Approach - Bin Xiao; Wei Li; Gang Guo; BoSheng Li; Zhen Liu; KeRan Jia; Ying Guo; XuHu Mao; QuanMing Zou (Current Microbiology, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Gene expression profiles associated with intersubgenomic heterosis in Brassica napus - Xin Chen; Maoteng Li; Jiaqin Shi; Donghui Fu; Wei Qian; Jun Zou; Chunyu Zhang; Jinling Meng (Theoretical and Applied Genetics, 2008)

Involvement of JNK regulation in oxidative stress-mediated murine liver injury by microcystin-LR - Yinna Wei; Dan Weng; Feng Li; Xiao Zou; D. Owen Young; Jianguo Ji; Pingping Shen (Apoptosis, 2008)